Secondary batteries, battery packs, vehicle and stationary power sources
Patent Information
- Application Number
- JP2020086640
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-19
- Filing Date
- 2020-05-18
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-05-18
Smart Images

Figure 0007652541000010 
Figure 0007652541000011 
Figure 0007652541000012
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a separator, an electrode group, a secondary battery, a battery pack, a vehicle, and a stationary power source. [Background technology]
[0002] Non-aqueous electrolyte batteries such as lithium ion secondary batteries are used as power sources in a wide range of fields. The form of non-aqueous electrolyte batteries ranges from small ones for various electronic devices to large ones for electric vehicles. The non-aqueous electrolyte battery includes a negative electrode containing a negative electrode active material, a positive electrode containing a positive electrode active material, a separator, and a non-aqueous electrolyte. For example, a carbon material or lithium titanium oxide is used as the negative electrode active material. For example, a layered oxide containing nickel, cobalt, manganese, etc. is used as the positive electrode active material. For example, a resin porous film or nonwoven fabric is used as the separator. For example, a liquid non-aqueous electrolyte in which an electrolyte salt is dissolved in a non-aqueous solvent can be used as the non-aqueous electrolyte. For example, a mixture of ethylene carbonate and methyl ethyl carbonate is used as the non-aqueous solvent. The non-aqueous electrolyte has high oxidation resistance and reduction resistance, and electrolysis of the solvent is unlikely to occur. Therefore, the non-aqueous electrolyte battery can achieve high electromotive force and excellent charge / discharge performance. However, since many non-aqueous solvents are flammable substances, various measures to improve safety are required for non-aqueous electrolyte batteries.
[0003] On the other hand, nickel-metal hydride batteries and lead-acid batteries are examples of batteries that use aqueous electrolytes, which are made by dissolving electrolyte salts in an aqueous solvent. Aqueous solvents are generally non-flammable substances. Therefore, by using an aqueous electrolyte, a battery with higher safety can be obtained compared to a battery that uses a non-aqueous electrolyte.
[0004] However, the water contained in the aqueous solvent has a narrower potential window for electrolysis than a non-aqueous solvent, and therefore aqueous electrolyte batteries have a problem of low charge / discharge efficiency due to the electrolysis of water. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-173956 A [Patent Document 2] JP 2013-232284 A [Patent Document 3] Special Publication No. 2016-512649 [Patent Document 4] JP 2015-32535 A [Patent Document 5] US Patent Application Publication No. 2012 / 251891 [Non-patent literature]
[0006] [Non-Patent Document 1] S. Liu and 4 others, "Rechargeable Aqueous Lithium-Ion Battery of TiO2 / LiMn2O4with a High Voltage", Journal of the Electrochemical Society, 2011, 158 (12) A1490-A1497 Summary of the Invention [Problem to be solved by the invention]
[0007] The problem that the present invention aims to solve is to provide a separator, an electrode group, a secondary battery, and a battery pack, a vehicle, and a stationary power source each including this secondary battery, which realize a secondary battery having low resistance and long life characteristics. [Means for solving the problem]
[0008] According to an embodiment, a separator is provided, the separator includes an inorganic particle layer including inorganic particles, a polymer binder, and a fibrous material, and the ratio of the mass of the fibrous material to the total mass of the inorganic particles, the polymer binder, and the fibrous material is 0.1 mass% or more and 40 mass% or less. The ratio of the mass of the polymer binder to the total mass of the inorganic particles, the polymer binder and the fibrous material is 5% by mass to 30% by mass, and the average fiber diameter of the fibrous material is 1 nm to 30 nm. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a cross-sectional view showing the separator according to the first embodiment. [Diagram 2] FIG. 6 is a schematic diagram of an electrode group according to a second embodiment. [Diagram 3] FIG. 11 is a cross-sectional view illustrating an example of a secondary battery according to a third embodiment. [Figure 4] FIG. 11 is a cross-sectional view illustrating a schematic configuration of another example of the secondary battery according to the third embodiment. [Diagram 5] 5 is a cross-sectional view taken along line III-III of the secondary battery shown in FIG. 4. [Figure 6] FIG. 11 is a partially cutaway perspective view that illustrates a schematic diagram of still another example of a secondary battery according to the third embodiment. [Figure 7] FIG. 7 is an enlarged cross-sectional view of a portion B of the secondary battery shown in FIG. 6. [Figure 8] FIG. 13 is a perspective view illustrating an example of a battery pack according to a fourth embodiment. [Figure 9] FIG. 13 is an exploded perspective view illustrating an example of a battery pack according to a fifth embodiment. [Figure 10] 10 is a block diagram showing an example of an electric circuit of the battery pack shown in FIG. 9. [Figure 11] FIG. 13 is a cross-sectional view illustrating an example of a vehicle according to a sixth embodiment. [Figure 12] FIG. 13 is a block diagram showing an example of a system including a stationary power supply according to a seventh embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Items with the same reference numerals correspond to each other. The drawings are schematic or conceptual, and the relationship between the thickness and width of each part, the size ratio between parts, etc. are not necessarily the same as in reality. Even when the same part is shown, the dimensions and ratios may be shown differently depending on the drawing. In the following description, unless otherwise specified, pH is indicated at 25°C and 1 atmosphere (atmosphere).
[0011] (First embodiment)
[0012] FIG. 1 is a cross-sectional view showing a separator according to a first embodiment. The separator 53 shown in FIG. 1a includes an inorganic particle layer 531, and the inorganic particle layer 531 includes a fibrous material 534, inorganic particles 532, and a polymer binder 533. The polymer binder 533 is present in the gaps between the inorganic particles 532. The separator 53 shown in FIG. 1b includes an inorganic particle layer 531 and a porous free-standing film 530. The polymer binder 533 is included not only in the inorganic particle layer 531 but also in the porous free-standing film 530. The fibrous material 534 and the polymer binder 533 are present between the inorganic particle layer 531. The polymer binder 533 bonds the inorganic particles 532 to each other or between the inorganic particles 532 and the fibrous material 534. The separator according to the first embodiment includes inorganic particles, a polymer binder, and a fibrous material, and the ratio of the mass of the fibrous material to the total mass of the inorganic particles, the polymer binder, and the fibrous material is 0.1% by mass or more and 40% by mass or less. The ratio of the mass of the fibrous material to the total mass of the inorganic particles, the polymer binder, and the fibrous material can be expressed as {mass of the fibrous material ÷ (mass of the inorganic particles + mass of the polymer binder + mass of the fibrous material)} × 100. The inorganic particles are preferably ceramics having alkali ion conductivity such as lithium ions, but may be mixed with insulating metal oxides. In the case of FIG. 1b, the ratio of the mass of the fibrous material to the total mass of the inorganic particles, the polymer binder, and the fibrous material in the separator body excluding the porous self-supporting membrane may be 0.1% by mass or more and 40% by mass or less.
[0013] In a secondary battery having a solvent containing water as a solvent, the water contained in the solvent of the aqueous electrolyte may be electrolyzed inside and near the negative electrode during the initial charge. This is because the potential of the negative electrode decreases due to the absorption of lithium ions in the negative electrode active material during the initial charge. When the negative electrode potential decreases below the hydrogen generation potential, a part of the water is decomposed into hydrogen (H2) and hydroxide ions (OH-) inside and near the negative electrode. This increases the pH of the aqueous electrolyte present inside and near the negative electrode.
[0014] The hydrogen generation potential of the negative electrode depends on the pH of the aqueous electrolyte. In other words, as the pH of the aqueous electrolyte in contact with the negative electrode increases, the hydrogen generation potential of the negative electrode decreases. Therefore, after the first charge, water decomposition at the negative electrode becomes difficult to occur.
[0015] The separator according to the present embodiment uses a mixture of inorganic particles, a polymer binder, and a fibrous material. Therefore, it has a property that it allows alkali metal ions such as lithium ions to pass through but does not allow aqueous solvents to pass through easily. Therefore, in a secondary battery having the separator according to the first embodiment, the separator is located at least between the negative electrode and the positive electrode, so that the solvent contained in the aqueous electrolyte in contact with the negative electrode and the solvent contained in the aqueous electrolyte in contact with the positive electrode do not easily pass between each other. Therefore, in the secondary battery according to the first embodiment, the pH of the aqueous electrolyte in contact with the negative electrode can be maintained at a high level. Therefore, in a secondary battery having the separator according to the first embodiment, the electrolysis of water in the negative electrode is suppressed, and high charge / discharge efficiency, i.e., a long life, can be achieved.
[0016] The separator according to the present embodiment includes a fibrous material, which reduces the resistance of the separator and improves ion conductivity. This is presumably because the ion mobility of ions passing through the separator is improved by the incorporation of an aqueous electrolyte between the fibrous materials included in the separator. The incorporation of an aqueous electrolyte into the separator improves ion mobility, thereby suppressing the interfacial resistance between inorganic particles. The incorporation of an aqueous electrolyte between the fibers of the fibrous material included in the separator may hereinafter be referred to as swelling. Even if the separator swells, the average fiber diameter of the fibrous material remains almost unchanged.
[0017] In this way, by incorporating an aqueous electrolyte between the fibers of the fibrous material, a secondary battery having the separator according to the first embodiment can achieve low resistance. By reducing the resistance of the separator of the secondary battery or the secondary battery, it is possible to realize high-rate charge / discharge operations during charging / discharging, and further to reduce the internal resistance of the secondary battery. In this way, a secondary battery with reduced resistance can achieve high charge / discharge efficiency, that is, a long life. As described above, a secondary battery having the separator according to the first embodiment can achieve low resistance and long life characteristics.
[0018] Furthermore, by providing the separator according to this embodiment, it is possible to reduce the thickness while suppressing internal short circuits and water movement between the positive electrode and the negative electrode, and therefore it is also possible to increase the energy density.
[0019] By providing the separator according to this embodiment, it is possible to increase the proportion of the polymer binder in the separator while suppressing the resistance of the separator, thereby imparting flexibility to the separator, i.e., improving the mechanical strength.
[0020] The separator according to the first embodiment will be specifically described. The separator has electrical insulation properties and prevents the negative electrode and the positive electrode from coming into contact with each other to cause an internal short circuit. The separator is located at least between the positive electrode and the negative electrode. The separator is preferably in contact with the negative electrode, and more preferably in contact with both the positive electrode and the negative electrode. The separator is preferably located so as to cover the main surface of the negative electrode. In addition, the separator preferably covers one or more side surfaces in addition to the main surface of the negative electrode. By adopting such a configuration, the negative electrode side and the positive electrode side can be more accurately separated in the secondary battery, and the electrolysis of water can be more suppressed. The secondary battery according to the first embodiment may include a plurality of separators. In this case, the negative electrode and the positive electrode can be located between the separators.
[0021] The fibrous material of the separator preferably has a hydrophilic functional group such as a hydroxyl group, a sulfone group, or a carboxyl group, and examples thereof include cellulose fibers, polysaccharides, polyvinyl alcohol, polyacrylic acid, anionic derivatives of polystyrene such as polystyrene sulfonate, cationic derivatives of polystyrene such as polystyrene trialkylbenzylammonium, and derivatives and copolymers thereof. Among these, cellulose fibers are preferred. One type of fibrous material may be used alone, or two or more types may be mixed together. In this way, when the fibrous material has an electrically negative functional group such as a hydroxyl group, a sulfone group, or a carboxyl group, an electrolyte is taken in between the fibrous materials, causing the separator to swell.
[0022] The mass ratio of the fibrous material to the total mass of the inorganic particles, polymer binder and fibrous material contained in the separator is preferably 0.1% by mass or more and 40% by mass or less. In this range, the aqueous electrolyte is easily incorporated between the fibrous materials, the resistance of the separator can be reduced, and the mechanical strength of the separator can be maintained, thereby realizing a secondary battery with a long life. If the mass ratio of the fibrous material is less than 0.1% by mass, the amount of the fibrous material is small, so that the aqueous electrolyte is difficult to be incorporated between the fibrous materials, and it is difficult to reduce the resistance of the separator. If the mass ratio is more than 40% by mass, the fibrous material is excessively incorporated into the separator, so that the resistance can be reduced, but the mechanical strength of the separator decreases and the life characteristics of the secondary battery decrease. More preferably, it is 0.5% by mass or more and 30% by mass or less, and even more preferably, it is 1% by mass or more and 20% by mass or less. By ensuring that the content is within these ranges, the mechanical strength of the separator is not impaired, and the aqueous electrolyte is incorporated between the fibrous materials, thereby achieving low resistance of the separator and long life characteristics by maintaining the mechanical strength of the separator.
[0023] The mass ratio of the fibrous material, the mass ratio of the inorganic particles, and the mass ratio of the polymer binder relative to the total mass of the inorganic particles, the polymer binder, and the fibrous material can be calculated, for example, by the following method.
[0024] First, the secondary battery is disassembled and the separator is taken. Then, a part of this separator is cut out to obtain a test piece. The size of the test piece is, for example, a square plate with a side length of 2 cm. The test piece is thoroughly dried in advance under conditions such as 50 degrees Celsius in the atmosphere. Next, the test piece is mixed with a sufficient amount of solvent. The solvent used is one that does not dissolve the inorganic particles and fibrous material but can dissolve the polymer binder. For example, N-methyl-2-pyrrolidone (NMP) can be used to dissolve the polymer binder polyvinyl butyral (PVB). After the polymer binder is dissolved, a centrifuge is used to separate the solid content from the solvent in which the fibrous material has dissolved. At this time, the solid content contains the inorganic particles and fibrous material, and the solution contains the solvent and the polymer binder. The solid content is thoroughly dried and then subjected to thermal gravimetric analysis (TG) to obtain the mass of the inorganic particles and polymer binder contained in the solid content.
[0025] On the other hand, thermogravimetric analysis (TG) is performed on the solution to obtain the mass of the solvent and polymer binder contained in the solution. From the masses obtained above, the mass ratio of the fibrous material, the mass ratio of the inorganic particles, and the mass ratio of the polymer binder relative to the total of the inorganic particles, the polymer binder, and the fibrous material can be obtained.
[0026] When the composite electrolyte layer is provided on the porous free-standing membrane as shown in Fig. 1b, the nonwoven fabric is peeled off from the separator using a spatula or the like, and the mass of the separator is weighed, for example, using an electronic balance, and mixed with a sufficient amount of pure water. Next, the filtrate is collected by filtration, the pure water contained in the filtrate is evaporated, and the residue is subjected to thermogravimetric analysis (TG).
[0027] From the viewpoint of swelling the separator, the average fiber diameter of the fibrous material is preferably 100 nm or less, more preferably 30 nm or less. The lower limit of the average fiber diameter of the fibrous material is not particularly specified, but is preferably 0.1 nm or more, and more preferably 1 nm or more. The average fiber length of the fibrous material is not particularly specified, but can be 0.1 μm or more and 100 μm or less.
[0028] The average fiber diameter of the fibrous material can be measured, for example, by observation with a scanning electron microscope (SEM). The fabricated secondary battery is disassembled, and the separator is collected. The separator is thoroughly dried in advance, for example, under conditions of 50°C in air. The dried separator surface is gold sputtered and then observed using an SEM. The fiber diameter of the fibrous material seen in the SEM photograph is measured at 10 locations, and the average of these measurements is calculated as the average fiber diameter. The average fiber length of the fibrous material can also be measured in the same manner as the average fiber diameter.
[0029] The inorganic particles, polymer binder, and fibrous material contained in the separator according to the first embodiment will be specifically described.
[0030] The inorganic particles of the separator are compounds containing at least one type of cation selected from the group consisting of the following elements: Mg, Al, Si, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, In, Ba, Hf, Ta, W, Re, Ir, Pt, and Au. Examples of the compounds include, but are not limited to, oxides, sulfides, hydroxides, carbonates, and sulfates.
[0031] The inorganic particles are preferably inorganic solid electrolytes with excellent alkali ion conductivity. The inorganic particles preferably have high water resistance. This is because hydrolysis is less likely to occur in the secondary battery. The inorganic particles include, for example, lithium phosphate solid electrolytes having a NASICON-type structure and represented by the general formula LiM2(PO4)3 as inorganic solid electrolytes with excellent lithium ion conductivity. M in the above general formula is preferably at least one element selected from the group consisting of titanium (Ti), germanium (Ge), strontium (Sr), zirconium (Zr), tin (Sn), and aluminum (Al). It is more preferable that the element M contains any one of Ge, Zr, and Ti and Al.
[0032] Specific examples of the lithium phosphate solid electrolyte having a NASICON-type structure include LATP (Li 1+x Al x Ti 2-x (PO4)3), Li 1+x Al x Ge 2-x (PO4)3, Li 1+x Al x Zr 2-x (PO4)3. X in the above formula is in the range of 0 < x ≤ 5, and preferably in the range of 0.1 ≤ x ≤ 0.5. As the solid electrolyte, it is preferable to use LATP. LATP has excellent water resistance and is less likely to cause hydrolysis in the secondary battery.
[0033] In addition, as the oxide-based solid electrolyte, amorphous LIPON (Li 2.9 PO 3.3 N 0.46 ), or garnet-type structure LLZ (Li7La3Zr2O 12 ) may be used. The inorganic solid electrolyte may be one type, or two or more types may be mixed and used.
[0034] As the inorganic particles, a solid electrolyte that conducts sodium ions may be used. The sodium-containing solid electrolyte has excellent ion conductivity of sodium ions. Examples of the sodium-containing solid electrolyte include sodium phosphorus sulfide and sodium phosphorus oxide. The sodium ion-containing solid electrolyte is preferably in the form of glass ceramics.
[0035] Examples of inorganic particles include, but are not limited to, oxide ceramics such as alumina, silica, zirconia, yttria, magnesium oxide, calcium oxide, barium oxide, strontium oxide, and vanadium oxide, carbonates and sulfates such as sodium carbonate, potassium carbonate, magnesium carbonate, calcium carbonate, barium carbonate, lanthanum carbonate, cerium carbonate, calcium sulfate, magnesium sulfate, aluminum sulfate, gypsum, and barium sulfate, phosphates such as hydroxyapatite, zirconium phosphate, and titanium phosphate, and nitride ceramics such as silicon nitride, titanium nitride, and boron nitride. The inorganic particles listed above may be in the form of a hydrate.
[0036] The inorganic particles of alumina (Al2O3), silica (SiO2), and calcium oxide (CaO) are preferably in the form of glass ceramics. The metal oxide may be one type or may be a mixture of two or more types. The inorganic particles may be a mixture of an inorganic solid electrolyte and a metal oxide.
[0037] The shape of the inorganic particles is not particularly limited, but can be, for example, spherical, elliptical, flat, or fibrous. From the viewpoint of increasing alkali metal ion conductivity, the average particle size of the inorganic particles is preferably 100 μm or less, more preferably 70 μm or less, and even more preferably 50 μm or less. There is no particular lower limit to the average particle size of the inorganic particles, but in one example, it is 0.05 μm or more.
[0038] The average particle size of inorganic particles means the particle size at which the volumetric integrated value is 50% in the particle size distribution obtained by a laser diffraction particle size distribution measuring device. As a sample for this particle size distribution measurement, a dispersion diluted with ethanol so that the concentration of inorganic particles is 0.01% by mass to 5% by mass is used.
[0039] Monovalent cations can pass through the bulk or grain boundaries of inorganic particles in the separator, or through the aqueous electrolyte soaked into the separator. Examples of monovalent cations include alkali metal ions such as lithium ions, sodium ions, and potassium ions. On the other hand, in the separator, the aqueous electrolyte is taken up between the fibrous materials, causing the separator to swell, making it difficult for the solvent of the aqueous electrolyte to pass through. That is, solvated alkali metal ions can enter the separator, but the solvated alkali metal ions can be desolvated and pass through the separator.
[0040] The proportion of inorganic particles in the separator is typically 40 mass % or more and 90 mass % or less, for example, 45 mass % or more and 85 mass % or less.
[0041] The inorganic particles are preferably the main component of the separator. From the viewpoint of densifying the separator and improving water-blocking properties, the ratio of the inorganic particles in the separator is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. If the ratio of the inorganic particles in the separator is less than 60% by mass, the water-blocking properties are reduced.
[0042] From the viewpoint of increasing the flexibility of the separator, the proportion of inorganic particles in the separator is preferably 94% by mass or less, more preferably 92% by mass or less, and even more preferably 90% by mass or less. If the proportion of inorganic particles in the separator is more than 94% by mass, the proportion of the polymer binder is reduced to less than 6% by mass, which reduces flexibility and causes cracks in the separator, thereby reducing battery performance.
[0043] The proportion of inorganic particles in the entire separator can be calculated by thermogravimetric analysis (TG).
[0044] The polymer binder provided in the separator is configured as follows. The weight average molecular weight of the polymer binder is, for example, 3000 or more. When the weight average molecular weight of the polymer binder is 3000 or more, the binding property of the inorganic particles can be further improved. The weight average molecular weight of the polymer binder is preferably 3000 or more and 5,000,000 or less, more preferably 5000 or more and 2,000,000 or less, and even more preferably 10,000 or more and 1,000,000 or less. The weight average molecular weight of the polymer binder can be determined by gel permeation chromatography (GPC).
[0045] The polymer binder may be a polymer made of a single monomer unit, a copolymer made of a plurality of monomer units, or a mixture thereof. The polymer binder preferably contains a monomer unit made of a hydrocarbon having a functional group containing one or more elements selected from the group consisting of oxygen (O), sulfur (S), nitrogen (N), and fluorine (F). In the polymer binder, the proportion of the portion made of the monomer unit is preferably 70 mol % or more. Hereinafter, this monomer unit is referred to as a first monomer unit. In addition, in the copolymer, the one other than the first monomer unit is referred to as a second monomer unit. The copolymer of the first monomer unit and the second monomer unit may be an alternating copolymer, a random copolymer, or a block copolymer.
[0046] If the proportion of the portion constituted by the first monomer unit in the polymer binder is lower than 70 mol %, the separator becomes more permeable to water, which may result in a decrease in the charge / discharge efficiency of the battery. In the polymer binder, the proportion of the portion constituted by the first monomer unit is preferably 90 mol % or more. It is most preferable that the proportion of the portion constituted by the first monomer unit is 100 mol %, that is, the polymer is composed only of the first monomer unit.
[0047] The first monomer unit may be a compound having a functional group in a side chain containing one or more elements selected from the group consisting of oxygen (O), sulfur (S), nitrogen (N), and fluorine (F), and a main chain formed of a carbon-carbon bond. The hydrocarbon may have one or more functional groups containing one or more elements selected from the group consisting of oxygen (O), sulfur (S), nitrogen (N), and fluorine (F). The functional group in the first monomer unit increases the conductivity of alkali metal ions passing through the separator.
[0048] The hydrocarbon constituting the first monomer unit preferably has a functional group containing at least one element selected from the group consisting of oxygen (O), sulfur (S), and nitrogen (N). When the first monomer unit has such a functional group, the conductivity of alkali metal ions in the separator tends to be increased, and the internal resistance tends to be reduced.
[0049] The functional group contained in the first monomer unit is preferably at least one selected from the group consisting of a formal group, a butyral group, a carboxymethyl ester group, an acetyl group, a carbonyl group, a hydroxyl group, and a fluoro group. The first monomer unit more preferably contains at least one of a carbonyl group and a hydroxyl group in the functional group, and even more preferably contains both.
[0050] The first monomer unit can be represented by the following formula: [ka]
[0051] In the above formula, R1 is preferably selected from the group consisting of hydrogen (H), an alkyl group, and an amino group. R2 is preferably selected from the group consisting of a hydroxyl group (-OH), -OR1, -COOR1, -OCOR1, -OCH(R1)O-, -CN, -N(R1)3, and -SO2R1. Examples of the first monomer unit include at least one or more selected from the group consisting of vinyl formal, vinyl alcohol, vinyl acetate, vinyl acetal, vinyl butyral, acrylic acid and its derivatives, methacrylic acid and its derivatives, acrylonitrile, acrylamide and its derivatives, styrene sulfonic acid, and tetrafluoroethylene.
[0052] The polymer binder preferably contains at least one selected from the group consisting of polyvinyl formal, polyvinyl alcohol, polyvinyl acetal, polyvinyl butyral, polymethyl methacrylate, and polytetrafluoroethylene.
[0053] An example of the structural formula of a compound that can be used as a polymer binder is shown below. The structural formula of polyvinyl formal is as follows. In the following formula, it is preferable that a is 50 or more and 80 or less, b is 0 or more and 5 or less, and c is 15 or more and 50 or less. [ka]
[0054] The structural formula of polyvinyl butyral is as follows: In the following formula, it is preferable that l is 50 or more and 80 or less, m is 0 or more and 10 or less, and n is 10 or more and 50 or less. [ka]
[0055] The structural formula of polyvinyl alcohol is as follows: In the following formula, n is preferably 70 or more and 20,000 or less. [ka]
[0056] The structural formula of polymethyl methacrylate is as follows: In the following formula, n is preferably 30 or more and 10,000 or less. [ka]
[0057] The second monomer unit is a compound other than the first monomer unit, i.e., a compound that does not have a functional group containing one or more elements selected from the group consisting of oxygen (O), sulfur (S), nitrogen (N), and fluorine (F), or a compound that has such a functional group but is not a hydrocarbon. Examples of the second monomer unit include ethylene oxide and styrene. Examples of the polymer composed of the second monomer unit include polyethylene oxide (PEO) and polystyrene (PS).
[0058] The types of functional groups contained in the first monomer unit and the second monomer unit can be identified by infrared spectroscopy (Fourier Transform Infrared Spectroscopy; FT-IR). Furthermore, it can be determined that the first monomer unit is composed of a hydrocarbon by nuclear magnetic resonance (NMR). Furthermore, the proportion of the portion composed of the first monomer unit in a copolymer of the first monomer unit and the second monomer unit can be calculated by NMR.
[0059] The polymer binder may contain an aqueous electrolyte. The proportion of the aqueous electrolyte that the polymer binder may contain can be understood by its water absorption rate. Here, the water absorption rate of the polymer binder is the value obtained by subtracting the mass M of the polymer binder before immersion from the mass M1 of the polymer binder after immersion in water at a temperature of 23°C for 24 hours, and dividing the result by the mass M of the polymer binder before immersion ([M1-M] / M×100). The water absorption rate of the polymer binder is considered to be related to the polarity of the polymer binder.
[0060] When a polymer binder with high water absorption is used, the alkali metal ion conductivity of the separator tends to increase. In addition, when a polymer binder with high water absorption is used, the binding force between the inorganic particles and the polymer binder is increased, so that the flexibility of the separator can be increased. The water absorption of the polymer binder is preferably 0.01% or more, more preferably 0.5% or more, and further preferably 2% or more.
[0061] The strength of the separator can be increased by using a polymer binder with a low water absorption rate. In other words, if the water absorption rate of the polymer binder is too high, the polymer binder of the separator may flow into the aqueous electrolyte. The water absorption rate of the polymer binder is preferably 15% or less, more preferably 10% or less, even more preferably 7% or less, and particularly preferably 3% or less.
[0062] The proportion of the polymer binder in the separator is typically 5% by mass or more and 30% by mass or less, or 5% by mass or more and 20% by mass or less.
[0063] From the viewpoint of increasing the flexibility of the separator, the proportion of the polymer binder in the separator is preferably 1 mass % or more, more preferably 3 mass % or more, and more preferably 10 mass % or more.
[0064] From the viewpoint of increasing the lithium ion conductivity of the separator, the ratio of the polymer binder in the separator is preferably 50 mass % or less, more preferably 40 mass % or less, and further preferably 30 mass % or less. The ratio of the polymer binder in the entire separator can be calculated by thermogravimetry (TG) analysis.
[0065] The separator may contain a plasticizer and an electrolyte salt in addition to the inorganic particles, the fibrous material, and the polymer binder. When the separator contains an electrolyte salt, the alkali metal ion conductivity of the separator can be further increased.
[0066] The proportion of the electrolyte salt in the separator is preferably 0.01% by mass to 10% by mass, and more preferably 0.05% by mass to 5% by mass. The proportion of the electrolyte salt in the separator can be calculated by thermogravimetry (TG) analysis.
[0067] The fact that the separator contains an electrolyte salt can be confirmed, for example, by the distribution of alkali metal ions obtained by energy dispersive X-ray spectrometry (EDX) of a separator cross section. That is, when the separator is made of a material that does not contain electrolyte salt, the alkali metal ions remain on the surface layer of the polymer in the separator, and are hardly present inside the separator. Therefore, a concentration gradient can be observed in which the concentration of alkali metal ions is high on the surface layer of the separator and low inside the separator. On the other hand, when the separator is made of a material that contains electrolyte salt, it can be confirmed that the alkali metal ions are uniformly present even inside the separator.
[0068] When the electrolyte salt contained in the separator and the electrolyte salt contained in the aqueous electrolyte are different, the difference in the types of ions present indicates that the separator contains an electrolyte salt different from that of the aqueous electrolyte. For example, when lithium chloride (LiCl) is used as the aqueous electrolyte and LiTFSI (lithium bis(fluorosulfonyl)imide) is used as the separator, the presence of (fluorosulfonyl)imide ions can be confirmed in the separator. On the other hand, the presence of (fluorosulfonyl)imide ions cannot be confirmed in the aqueous electrolyte on the negative electrode side, or they are present at an extremely low concentration.
[0069] As the electrolyte salt, it is preferable to use a lithium salt, a sodium salt, or a mixture thereof. As the electrolyte salt, one or more kinds can be used. As the lithium salt, for example, lithium chloride (LiCl), lithium bromide (LiBr), lithium hydroxide (LiOH), lithium sulfate (Li2SO4), lithium nitrate (LiNO3), lithium acetate (CH3COOLi), lithium oxalate (Li2C2O4), lithium carbonate (Li2CO3), lithium bis(trifluoromethanesulfonyl)imide) (LiTFSI; LiN(SO2CF3)2), lithium bis(fluorosulfonyl)imide (LiFSI; LiN(SO2F)2), and lithium bisoxalate borate (LiBOB: LiB[(OCO)2]2) can be used.
[0070] As the sodium salt, sodium chloride (NaCl), sodium sulfate (Na2SO4), sodium hydroxide (NaOH), sodium nitrate (NaNO3), sodium trifluoromethanesulfonylamide (NaTFSA), and the like can be used.
[0071] As described above, the fibrous material of the separator preferably has a hydrophilic functional group such as a hydroxyl group, a sulfone group, or a carboxyl group, and examples thereof include cellulose fiber, polysaccharides, anionic derivatives of polystyrene such as polyvinyl alcohol, polyacrylic acid, and polystyrene sulfonate, cationic derivatives of polystyrene such as polystyrene trialkylbenzylammonium, and derivatives and copolymers thereof. Among these, cellulose fiber is preferable. One type of fibrous material may be used alone, or two or more types may be mixed together. In this way, when the fibrous material has an electrically negative functional group such as a hydroxyl group, a sulfone group, or a carboxyl group, an electrolyte is taken in between the fibrous material and the separator can swell.
[0072] From the viewpoint of swelling the separator, the average fiber diameter of the fibrous material is preferably 100 nm or less, more preferably 30 nm or less. The lower limit of the average fiber diameter of the fibrous material is not particularly specified, but is preferably 0.1 nm or more, and more preferably 1 nm or more. The average fiber length of the fibrous material is not particularly specified, but can be 0.1 μm or more and 100 μm or less.
[0073] The separator is preferably flexible. If the separator is flexible, defects such as cracks are less likely to occur in the separator. Therefore, if a flexible separator is used, the negative electrode side and the positive electrode side can be more accurately separated in the secondary battery, and the electrolysis of water can be more effectively suppressed. The degree of flexibility of the separator may depend on the type and amount of the polymer binder contained in the separator.
[0074] The thickness of the separator is preferably 1 μm or more and 100 μm or less as the thickness of the inorganic particle layer. By being in this range, the energy density of the secondary battery can be increased and the mechanical strength can be maintained. If it is less than 1 μm, the internal resistance of the secondary battery decreases and the volumetric energy density of the secondary battery tends to increase, but it is not preferable because it is difficult to suppress the permeation of the electrolyte. If it is more than 100 μm, it is difficult to permeate the aqueous solvent, and the life of the secondary battery can be increased, but the energy density decreases. More preferably, it is 2 μm or more and 80 μm or less, and even more preferably, it is 5 μm or more and 60 μm or less. The thickness of the separator can be measured, for example, by SEM observation. That is, first, the secondary battery is disassembled and the separator is taken. The separator is thoroughly dried in advance under conditions such as 50° C. in air. Next, a part of this separator is cut out to obtain a test piece. The size of the test piece is, for example, a square plate with a side length of 2 cm. The cross section of the obtained test piece is subjected to gold sputtering treatment, and then the cross section of the test piece is observed with an SEM to obtain the separator film thickness.
[0075] The separator can be used alone, but may be laminated on the surface of the porous free-standing membrane. This is, for example, the form shown in FIG. 1b. As a separator, the mechanical strength can be increased by laminating an inorganic particle layer on the surface of the porous free-standing membrane. That is, by laminating an inorganic particle layer on the surface of the porous free-standing membrane, it is possible to maintain the mechanical strength even if the inorganic particle layer is made thin. The thickness of the porous free-standing membrane is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 10 μm or less. When the inorganic particle layer and the porous free-standing membrane according to this embodiment are laminated and used, the thickness of the separator laminated with the porous free-standing membrane is preferably 200 μm at most. In this case, the thickness of the inorganic particle layer is in the thickness range described above, and the thickness of the porous free-standing membrane is also in the thickness range described above.
[0076] The porous free-standing membrane is, for example, a porous film or a nonwoven fabric. For example, polyethylene (PE), polypropylene (PP), cellulose, or polyvinylidene fluoride (PVdF) can be used as the material for the porous film or the nonwoven fabric. The porous film is preferably a cellulose nonwoven fabric.
[0077] The porous free-standing membrane may be impregnated with a non-aqueous electrolyte. The porous free-standing membrane may also include a polymeric binder.
[0078] Next, a method for manufacturing a separator will be described. First, inorganic particles, a polymer binder, a fibrous material, and a solvent are mixed to obtain a mixed liquid. In this mixed liquid, the mass ratio of the inorganic particles, the polymer binder, and the fibrous material is preferably 49:49:2 to 96:2:2. The mass ratio is expressed as the ratio of the mass of each to the total mass of the inorganic particles, the polymer binder, and the fibrous material. An electrolyte salt may be added to the mixed liquid as desired. In this case, the mass ratio of the inorganic particles, the polymer binder, the fibrous material, and the electrolyte salt in the mixed liquid is preferably 50:40:10 to 96:2:2.
[0079] As the solvent, it is preferable to use one capable of dissolving the polymer binder. Examples of the solvent include alcohols such as ethanol, methanol, isopropyl alcohol, normal propyl alcohol, and benzyl alcohol, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, and diacetone alcohol, esters such as ethyl acetate, methyl acetate, butyl acetate, ethyl lactate, methyl lactate, and butyl lactate, ethers such as methyl cellosolve, ethyl cellosolve, butyl cellosolve, 1,4-dioxane, and tetrahydrofuran, glycols such as ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, butyl carbitol acetate, and ethyl carbitol acetate, and methyl ether acetate. Examples of the solvent that can be used include glycol ethers such as tyl carbitol, ethyl carbitol, and butyl carbitol; aprotic polar solvents such as dimethylformamide, dimethylacetamide, acetonitrile, valeronitrile, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, and γ-butyrolactam; cyclic carboxylic acid esters such as gamma butyrolactone, gamma valerolactone, gamma caprolactone, and epsilon caprolactone; and chain carbonate compounds such as dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, ethyl methyl carbonate, and methyl-n-propyl carbonate.
[0080] The mixture is then thoroughly stirred using a dispersing machine such as a ball mill to obtain a slurry, which is then poured into a mold and the solvent is removed by vacuum drying to obtain a separator that contains at least inorganic particles, fibrous materials, and a polymer binder.
[0081] The separator can also be produced by coating a porous free-standing membrane as follows: For example, the above-mentioned slurry is coated onto the first main surface of the porous free-standing membrane by a doctor blade method.
[0082] The separator described above has a two-layer structure of a porous free-standing film and a layer containing inorganic particles, which is more preferable because it increases the mechanical strength of the separator, reduces the thickness of the separator, and reduces the internal resistance inside the secondary battery.
[0083] The separator according to the first embodiment includes an inorganic particle layer containing inorganic particles, a polymer binder, and a fibrous material, and the ratio of the mass of the fibrous material to the total mass of the inorganic particles, the polymer binder, and the fibrous material is 0.1% by mass or more and 40% by mass or less. By including the fibrous material, the resistance of the separator can be reduced, lithium ion conductivity can be improved, and the inorganic particles can suppress water migration. Therefore, a secondary battery including the separator according to the first embodiment can achieve low resistance and long life characteristics.
[0084] Second Embodiment The electrode group according to the second embodiment will be described with reference to Fig. 2. Fig. 2 is a schematic diagram of the electrode group according to the second embodiment. The electrode group 1 includes a positive electrode 5, a negative electrode 3, and a separator 4 according to the first embodiment between the positive electrode and the negative electrode.
[0085] The positive and negative electrodes of the electrode group will be described in detail below. The separator 4 has been described in the first embodiment, so a description thereof will be omitted.
[0086] (Negative electrode) The negative electrode may include a negative electrode current collector and a negative electrode active material-containing layer supported on at least one main surface of the negative electrode current collector.
[0087] The material of the negative electrode current collector is a substance that is electrochemically stable in the negative electrode potential range when the alkali metal ion is inserted or removed. The negative electrode current collector is preferably, for example, an aluminum foil or an aluminum alloy foil containing at least one element selected from magnesium (Mg), titanium (Ti), zinc (Zn), manganese (Mn), iron (Fe), copper (Cu) and silicon (Si). The negative electrode current collector may be in other forms such as a porous body or a mesh. The thickness of the negative electrode current collector is preferably 5 μm or more and 20 μm or less. A current collector having such a thickness can balance the strength and weight reduction of the electrode.
[0088] The negative electrode active material-containing layer contains a negative electrode active material. The negative electrode active material-containing layer may be supported on both main surfaces of the negative electrode current collector.
[0089] The porosity of the negative electrode active material-containing layer is preferably 20% or more and 50% or less. This allows a negative electrode with excellent affinity with the aqueous electrolyte and high density to be obtained. The porosity of the negative electrode active material-containing layer is more preferably 25% or more and 40% or less.
[0090] The porosity of the negative electrode active material-containing layer can be obtained, for example, by mercury intrusion porosimetry. Specifically, first, the pore distribution of the active material-containing layer is obtained by mercury intrusion porosimetry. Then, the total pore volume is calculated from this pore distribution. Then, the porosity can be calculated from the ratio of the total pore volume to the volume of the active material-containing layer.
[0091] The specific surface area of the negative electrode active material-containing layer measured by the BET method using nitrogen (N2) adsorption is 3m 2 / g or more 50m 2 / g or less. 2 If the specific surface area of the negative electrode active material-containing layer is less than 50 m / g, the affinity between the negative electrode active material and the aqueous electrolyte is reduced. As a result, the interface resistance of the negative electrode increases, and the output characteristics and the charge / discharge cycle characteristics may be deteriorated. 2If the content exceeds 1 / g, the distribution of ion species ionized from the electrolyte salt is biased toward the negative electrode, leading to a shortage of ion species ionized from the electrolyte salt at the positive electrode, which may result in a decrease in output characteristics and charge / discharge cycle characteristics.
[0092] The specific surface area can be obtained, for example, by the following method. First, the secondary battery is disassembled, and a part of the negative electrode active material-containing layer is collected. Next, in nitrogen gas at 77K (boiling point of nitrogen), the nitrogen gas pressure P (mmHg) is gradually increased, and the nitrogen gas adsorption amount (mL / g) of the sample is measured for each pressure P. Next, the pressure P (mmHg) is divided by the saturated vapor pressure P0 (mmHg) of nitrogen gas to obtain a relative pressure P / P0, and the nitrogen gas adsorption amount for each relative pressure P / P0 is plotted to obtain an adsorption isotherm. Next, a BET plot is calculated from this nitrogen adsorption isotherm and the BET formula, and the specific surface area is obtained using this BET plot. Note that the BET multipoint method is used to calculate the BET plot.
[0093] The negative electrode active material has a lithium ion absorption and release potential of 1V (vs. Li / Li) based on metallic lithium. + ) or more and 3V or less (vs.Li / Li + ) can be used. That is, as described above, the secondary battery according to the embodiment can maintain the hydrogen generation potential of the negative electrode at a low level after the first charge. Therefore, the negative electrode active material of this secondary battery can be one having a relatively low lower limit of the lithium ion absorption / release potential. By using such a negative electrode active material, the energy density of the secondary battery can be increased. Therefore, this secondary battery can achieve an energy density equivalent to that of a battery using a non-aqueous electrolyte.
[0094] Specifically, the negative electrode active material may be titanium oxide or a titanium-containing oxide. The titanium-containing oxide may be a lithium titanium composite oxide, a niobium titanium composite oxide, or a sodium niobium titanium composite oxide. The negative electrode active material may contain one or more of the titanium oxide and the titanium-containing oxide.
[0095] The titanium oxides include, for example, titanium oxides with a monoclinic structure, rutile structure titanium oxides, and anatase structure titanium oxides. The titanium oxides of each crystal structure have a composition before charging represented by TiO2 and a composition after charging represented by Li x TiO2 (where x is 0 ≤ x ≤ 1). Also, the structure before charging of the titanium oxide with a monoclinic structure can be represented as TiO2(B).
[0096] The lithium titanium oxides include, for example, lithium titanium oxides with a spinel structure (for example, the general formula Li 4+x Ti5O 12 (where x is -1 ≤ x ≤ 3)), lithium titanium oxides with a lamellarite structure (for example, Li 2+x Ti3O7 (-1 ≤ x ≤ 3)), Li 1+x Ti2O4 (0 ≤ x ≤ 1), Li 1.1+x Ti 1.8 O4 (0 ≤ x ≤ 1), Li 1.07+x Ti 1.86 O4 (0 ≤ x ≤ 1), Li x TiO2 (0 < x ≤ 1), etc. Also, the lithium titanium oxide may be a lithium titanium composite oxide into which a different element has been introduced.
[0097] The niobium titanium composite oxides include, for example, those represented by Li a TiM b Nb 2±β O 7±σ (0 ≤ a ≤ 5, 0 ≤ b ≤ 0.3, 0 ≤ β ≤ 0.3, 0 ≤ σ ≤ 0.3, and M is at least one element selected from the group consisting of Fe, V, Mo, and Ta).
[0098] The sodium niobium titanium composite oxides include, for example, those represented by the general formula Li 2+V Na 2―W M1 X Ti 6-y-z Nb y M2 z O 14+δIt contains an orthorhombic Na-containing niobium titanium composite oxide represented by (0≦v≦4, 0≦w<2, 0≦x<2, 0<y<6, 0≦z<3, -0.5≦δ≦0.5, M1 contains at least one selected from Cs, K, Sr, Ba, Ca, and M2 contains at least one selected from Zr, Sn, V, Ta, Mo, W, Fe, Co, Mn, Al).
[0099] As the negative electrode active material, it is preferable to use titanium oxide with anatase structure, titanium oxide with monoclinic structure, lithium titanium oxide with spinel structure, or a mixture thereof. When these oxides are used as the negative electrode active material, for example, by combining with a lithium manganese composite oxide as the positive electrode active material, a high electromotive force can be obtained.
[0100] The negative electrode active material is contained in the negative electrode active material-containing layer in the form of particles, for example. The negative electrode active material particles can be primary particles, secondary particles that are aggregates of primary particles, or a mixture of single primary particles and secondary particles. The shape of the particles is not particularly limited and can be, for example, spherical, elliptical, flat, and fibrous.
[0101] The secondary particles of the negative electrode active material can be obtained, for example, by the following method. First, a reaction synthesis of the active material raw material is carried out to produce an active material precursor with an average particle diameter of 1 μm or less. Then, the active material precursor is subjected to a firing treatment and a grinding treatment using a grinder such as a ball mill or a jet mill. Next, in the firing treatment, the active material precursor is aggregated and grown into secondary particles with a large particle diameter.
[0102] The average particle diameter (diameter) of the secondary particles of the negative electrode active material is preferably 3 μm or more, and more preferably 5 μm or more and 20 μm or less. In this range, since the surface area of the active material is small, the decomposition of water can be more suppressed.
[0103] The average particle size of the primary particles of the negative electrode active material is preferably 1 μm or less. This shortens the diffusion distance of Li ions inside the active material and increases the specific surface area. Therefore, excellent high input performance (fast charging) can be obtained. On the other hand, if the average particle size of the primary particles of the negative electrode active material is small, the particles are more likely to aggregate. If the particles of the negative electrode active material aggregate, the aqueous electrolyte in the secondary battery is more likely to be unevenly distributed in the negative electrode, which may lead to a depletion of ion species in the positive electrode. Therefore, the average particle size of the primary particles of the negative electrode active material is preferably 0.001 μm or more. It is more preferable that the average particle size of the primary particles of the negative electrode active material is 0.1 μm or more and 0.8 μm or less.
[0104] The primary particle size and secondary particle size refer to the particle size at which the volume cumulative value is 50% in the particle size distribution obtained by a laser diffraction particle size distribution measuring device. For example, Shimadzu SALD-300 is used as the laser diffraction particle size distribution measuring device. During the measurement, the light intensity distribution is measured 64 times at 2-second intervals. As a sample for this particle size distribution measurement, a dispersion diluted with N-methyl-2-pyrrolidone so that the concentration of the negative electrode active material particles is 0.1% by mass to 1% by mass is used. Alternatively, as a measurement sample, a dispersion containing 0.1 g of the negative electrode active material and a surfactant dispersed in 1 to 2 ml of distilled water is used.
[0105] The negative electrode active material has a specific surface area of, for example, 3 m2 as measured by the BET method using nitrogen (N2) adsorption. 2 / g or more 200m 2 / g or less. When the specific surface area of the negative electrode active material is within this range, the affinity between the negative electrode and the aqueous electrolyte can be further increased. This specific surface area can be determined, for example, by the same method as that for the specific surface area of the negative electrode active material-containing layer.
[0106] The negative electrode active material-containing layer may contain a conductive agent, a binder, and the like in addition to the negative electrode active material.
[0107] The conductive agent is mixed as necessary to improve the current collecting performance and suppress the contact resistance between the active material and the current collector. Examples of the conductive agent include carbonaceous materials such as acetylene black, ketjen black, graphite, and coke. The conductive agent may be one type or a mixture of two or more types.
[0108] The binder has the function of binding the active material, the conductive agent, and the current collector. As the binder, for example, at least one selected from the group consisting of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), and other cellulose-based polymers, fluorine-based rubber, styrene butadiene rubber, acrylic resin or its copolymer, polyacrylic acid, and polyacrylonitrile can be used, but is not limited thereto. The binder may be one type, or two or more types may be mixed and used.
[0109] The mixing ratios of the negative electrode active material, conductive agent, and binder in the negative electrode active material-containing layer are preferably in the ranges of 70% by mass or more and 95% by mass or less, 3% by mass or more and 20% by mass or less, and 2% by mass or more and 10% by mass or less. When the mixing ratio of the conductive agent is 3% by mass or more, the conductivity of the negative electrode can be improved, and when it is 20% by mass or less, the decomposition of the aqueous electrolyte on the conductive agent surface can be reduced. When the mixing ratio of the binder is 2% by mass or more, sufficient electrode strength can be obtained, and when it is 10% by mass or less, the insulating part of the electrode can be reduced.
[0110] The negative electrode can be obtained, for example, by the following method. First, an active material, a conductive agent, and a binder are suspended in an appropriate solvent to prepare a slurry. Then, this slurry is applied to one or both sides of a current collector. The coating on the current collector is dried to form an active material-containing layer. Then, the current collector and the active material-containing layer formed thereon are pressed. As the active material-containing layer, a mixture of an active material, a conductive agent, and a binder formed into a pellet shape may be used.
[0111] (positive electrode) The positive electrode may include a positive electrode current collector and a positive electrode active material-containing layer supported on at least one main surface of the positive electrode current collector.
[0112] The positive electrode current collector is made of a metal such as stainless steel, aluminum (Al), and titanium (Ti), for example. The positive electrode current collector is in the form of a foil, a porous body, or a mesh, for example. To prevent corrosion due to the reaction between the positive electrode current collector and the aqueous electrolyte, the surface of the positive electrode current collector may be coated with a different element. The positive electrode current collector is preferably excellent in corrosion resistance and oxidation resistance, such as Ti foil, for example. When Li2SO4 is used as the aqueous electrolyte, Al may be used as the positive electrode current collector because corrosion does not progress.
[0113] The positive electrode active material-containing layer contains a positive electrode active material. The positive electrode active material-containing layer may be supported on both main surfaces of the positive electrode current collector.
[0114] As the positive electrode active material, a compound having a lithium ion intercalation / deintercalation potential of 2.5 V (vs. Li / Li + ) or more and 5.5 V or less (vs. Li / Li + ) based on the potential of metallic lithium can be used. The positive electrode may contain one type of positive electrode active material or may contain two or more types of positive electrode active materials.
[0115] Examples of the positive electrode active material include lithium manganese composite oxide, lithium nickel composite oxide, lithium cobalt aluminum composite oxide, lithium nickel cobalt manganese composite oxide, spinel-type lithium manganese nickel composite oxide, lithium manganese cobalt composite oxide, lithium iron oxide, lithium fluorinated iron sulfate, phosphate compounds having an olivine crystal structure (for example, Li x FePO4 (0 < x ≦ 1), Li x MnPO4 (0 < x ≦ 1)), etc. Phosphate compounds having an olivine crystal structure are excellent in thermal stability.
[0116] Examples of the positive electrode active material that can obtain a high positive electrode potential include, for example, Li having a spinel structure xMn2O4(0 < x ≦ 1), Li x Lithium manganese composite oxides such as MnO2(0 < x ≦ 1), for example Li x Ni 1-y Al y Lithium nickel aluminum composite oxides such as O2(0 < x ≦ 1, 0 < y < 1), for example Li x Lithium cobalt composite oxides such as CoO2(0 < x ≦ 1), for example Li x Ni 1-y―z Co y Mn z Lithium nickel cobalt composite oxides such as O2(0 < x ≦ 1, 0 < y < 1, 0 ≦ z < 1), for example Li x Mn y Co 1-y Lithium manganese cobalt composite oxides such as O2(0 < x ≦ 1, 0 < y < 1), for example Li x Mn 1-y Ni y Spinel-type lithium manganese nickel composite oxides such as O4(0 < x ≦ 1, 0 < y < 2, 0 < 1 - y < 1), for example Li x FePO4(0 < x ≦ 1), Li x Fe 1-y Mn y PO4(0 < x ≦ 1, 0 ≦ y ≦ 1), Li x Lithium phosphates having an olivine structure such as CoPO4(0 < x ≦ 1), iron fluorosulfate (for example Li x FeSO4F(0 < x ≦ 1)) may be mentioned.
[0117] The positive electrode active material is preferably at least one selected from the group consisting of lithium cobalt composite oxides, lithium manganese composite oxides, and lithium phosphates having an olivine structure. The operating potential of these active materials is 3.5 V (vs. Li / Li + ) or more and 4.2 V (vs. Li / Li + ) or less. That is, the operating potential of these active materials is relatively high. By using these positive electrode active materials in combination with negative electrode active materials such as the above-mentioned spinel-type lithium titanate and anatase-type titanium oxide, a high battery voltage can be obtained.
[0118] The positive electrode active material is contained in the positive electrode in the form of particles, for example. The positive electrode active material particles may be single primary particles, secondary particles which are aggregates of primary particles, or a mixture of primary particles and secondary particles. The shape of the particles is not particularly limited, and may be, for example, spherical, elliptical, flat, or fibrous.
[0119] The average particle size (diameter) of the primary particles of the positive electrode active material is preferably 10 μm or less, more preferably 0.1 μm or more and 5 μm or less, and the average particle size (diameter) of the secondary particles of the positive electrode active material is preferably 100 μm or less, more preferably 10 μm or more and 50 μm or less.
[0120] The primary particle size and secondary particle size of the positive electrode active material can be measured in the same manner as for the negative electrode active material particles.
[0121] The positive electrode active material-containing layer may contain a conductive agent and a binder in addition to the positive electrode active material. The conductive agent is mixed as necessary to improve current collection performance and suppress contact resistance between the active material and the current collector. Examples of the conductive agent include carbonaceous materials such as acetylene black, ketjen black, graphite, and coke. The conductive agent may be one type, or two or more types may be mixed and used.
[0122] Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, ethylene-butadiene rubber, polypropylene (PP), polyethylene (PE), carboxymethyl cellulose (CMC), polyimide (PI), polyacrylimide (PAI), etc. One type of binder may be used, or two or more types may be mixed and used.
[0123] The compounding ratios of the positive electrode active material, conductive agent, and binder in the positive electrode active material-containing layer are preferably 70% by mass or more and 95% by mass or less, 3% by mass or more and 20% by mass or less, and 2% by mass or more and 10% by mass or less, respectively. When the compounding ratio of the conductive agent is 3% by mass or more, the conductivity of the positive electrode can be improved, and when it is 20% by mass or less, the decomposition of the aqueous electrolyte on the conductive agent surface can be reduced. When the compounding ratio of the binder is 2% by mass or more, sufficient electrode strength can be obtained, and when it is 10% by mass or less, the insulating part of the electrode can be reduced.
[0124] The positive electrode can be obtained, for example, by the following method. First, an active material, a conductive agent, and a binder are suspended in an appropriate solvent to prepare a slurry. Then, this slurry is applied to one or both sides of a current collector. The coating on the current collector is dried to form an active material-containing layer. Then, the current collector and the active material-containing layer formed thereon are pressed. As the active material-containing layer, a mixture of an active material, a conductive agent, and a binder formed into a pellet shape may be used.
[0125] The electrode group according to the second embodiment includes a negative electrode, a positive electrode, and the separator according to the first embodiment. Since the separator according to the first embodiment is included, the secondary battery including the electrode group according to the second embodiment can achieve high energy density and long life characteristics.
[0126] (Third embodiment) The secondary battery according to the third embodiment includes a positive electrode, a negative electrode, an aqueous electrolyte, and the separator according to the first embodiment between the positive electrode and the negative electrode. The secondary battery according to the third embodiment also includes the electrode group according to the second embodiment.
[0127] FIG. 3 is a cross-sectional view that shows an example of a secondary battery according to a third embodiment. The secondary battery 500 shown in FIG. 3 includes a negative electrode 51, a positive electrode 52, a separator 53, and an aqueous electrolyte AE. The secondary battery 500 shown in FIG. 1 is a lithium ion secondary battery. Here, a lithium ion secondary battery is taken as an example for explanation, but the type of alkali metal ion that the negative electrode and the positive electrode can occlude and release is not particularly limited. Examples of alkali metal ions other than lithium ions include sodium ions and potassium ions.
[0128] The negative electrode 51 includes a negative electrode current collector 510 and a negative electrode active material-containing layer 511 supported on one main surface of the negative electrode current collector 510. The positive electrode 52 includes a positive electrode current collector 520 and a positive electrode active material-containing layer 521 supported on one main surface of the positive electrode current collector 520.
[0129] The separator 53 is located between the negative electrode active material-containing layer 511 and the positive electrode active material-containing layer 521. The separator 53 divides the inside of the secondary battery 500 into a negative electrode 51 side where the negative electrode 51 is located and a positive electrode 52 side where the positive electrode 52 is located.
[0130] The aqueous electrolyte AE is present in a space located between the negative electrode current collector 510 and the positive electrode current collector 520. Examples of this space include pores in the negative electrode active material-containing layer 511 and the positive electrode active material-containing layer 521, interfaces between the negative electrode active material-containing layer 511 and the positive electrode active material-containing layer 521 and the separator 53, and voids in the separator 53. The aqueous electrolyte AE is an aqueous solution containing an aqueous solvent and an electrolyte salt dissolved in the aqueous solvent.
[0131] In FIG. 3, the aqueous electrolyte AE is shown to be present between the separator 53 and the negative electrode 51 and the positive electrode 52, but the separator may be in contact with at least one of the negative electrode and the positive electrode.
[0132] The separator included in the secondary battery according to the third embodiment has been described in the first embodiment, and therefore will not be described here. The negative electrode and the positive electrode described in the electrode group according to the second embodiment can be used, and therefore will not be described here. The aqueous electrolyte and the container will be described in detail below.
[0133] (aqueous electrolyte) The aqueous electrolyte contains an aqueous solvent and an electrolyte salt. The aqueous electrolyte is, for example, liquid. The liquid aqueous electrolyte is prepared by dissolving an electrolyte salt as a solute in an aqueous solvent.
[0134] The electrolyte salt may be, for example, a lithium salt, a sodium salt, or a mixture thereof. The lithium salt and the sodium salt may be the same as those contained in the separator. The lithium salt preferably contains LiCl. The use of LiCl can increase the lithium ion concentration of the aqueous electrolyte. The lithium salt preferably contains at least one of LiSO4 and LiOH in addition to LiCl.
[0135] The molar concentration of lithium ions in the aqueous electrolyte is preferably 3 mol / L or more, more preferably 6 mol / L or more, and even more preferably 12 mol / L or more. When the concentration of lithium ions in the aqueous electrolyte is high, electrolysis of the aqueous solvent in the negative electrode is easily suppressed, and hydrogen generation from the negative electrode tends to be small.
[0136] The aqueous electrolyte preferably contains 1 mol or more of the aqueous solvent per mol of the solute salt, and more preferably contains 3.5 mol or more of the aqueous solvent per mol of the solute salt.
[0137] Aqueous electrolytes contain chloride ions (Cl - ), hydroxide ion (OH - ), sulfate ion (SO4 2- ), nitrate ion (NO3 - ) is preferably contained.
[0138] The pH of the aqueous electrolyte is preferably 3 or more and 14 or less, and more preferably 4 or more and 13 or less.
[0139] In addition, the pH of the aqueous electrolyte is preferably different between the negative electrode side and the positive electrode side after the initial charge. In the secondary battery after the initial charge, the pH of the aqueous electrolyte on the negative electrode side is preferably 3 or more, more preferably 5 or more, and even more preferably 7 or more. In the secondary battery after the initial charge, the pH of the aqueous electrolyte on the positive electrode side is preferably in the range of 0 to 7, and more preferably 0 to 6.
[0140] The pH of the aqueous electrolyte on the negative electrode side and the aqueous electrolyte on the positive electrode side can be obtained, for example, by disassembling the secondary battery and measuring the pH of the aqueous electrolyte present between the separator and the negative electrode and between the aqueous electrolyte on the positive electrode side and the separator.
[0141] As the aqueous solvent, a solution containing water can be used. Here, the solution containing water may be pure water or a mixed solvent of water and an organic solvent.
[0142] The aqueous electrolyte may be a gel electrolyte. The gel electrolyte is prepared by mixing the above-mentioned liquid aqueous electrolyte with a polymer compound to form a composite. Examples of the polymer compound include polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), and polyethylene oxide (PEO).
[0143] The presence of water in aqueous electrolytes can be confirmed by GC-MS (Gas Chromatography - Mass Spectrometry) measurements. In addition, the salt concentration and water content in aqueous electrolytes can be measured, for example, by ICP (Inductively Coupled Plasma) emission spectrometry. The molar concentration (mol / L) can be calculated by weighing a specified amount of aqueous electrolyte and calculating the salt concentration contained therein. In addition, the number of moles of solute and solvent can be calculated by measuring the specific gravity of the aqueous electrolyte.
[0144] (container) The container that houses the positive electrode, the negative electrode, and the aqueous electrolyte may be a metal container, a laminate film container, or a resin container.
[0145] As the metal container, a metal can made of nickel, iron, stainless steel, etc., and having a rectangular or cylindrical shape can be used. As the resin container, a container made of polyethylene, polypropylene, etc. can be used.
[0146] The thickness of each of the resin container and the metal container is preferably within a range of 0.05 mm to 1 mm, more preferably 0.5 mm or less, and further preferably 0.3 mm or less.
[0147] Examples of the laminate film include a multi-layer film in which a metal layer is coated with a resin layer. Examples of the metal layer include stainless steel foil, aluminum foil, and aluminum alloy foil. Polymers such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET) can be used for the resin layer. The thickness of the laminate film is preferably within a range of 0.01 mm or more and 0.5 mm or less. The thickness of the laminate film is more preferably 0.2 mm or less.
[0148] (Details of secondary batteries) The secondary battery according to the present embodiment can be used in various forms such as a square, cylindrical, flat, thin, coin, etc. Also, it may be a secondary battery having a bipolar structure. A secondary battery having a bipolar structure has an advantage that a plurality of cells connected in series can be manufactured from one cell.
[0149] The secondary battery according to the first embodiment will be described in detail below with reference to FIGS.
[0150] Fig. 4 is a cross-sectional view illustrating a schematic configuration of another example of the secondary battery according to embodiment 1. Fig. 5 is a cross-sectional view taken along line III-III of the secondary battery illustrated in Fig. 3.
[0151] The electrode group 1 is housed in a rectangular cylindrical metal container 2. The electrode group 1 has a structure in which a positive electrode 5 and a negative electrode 3 are spirally wound to have a flat shape with a separator 4 interposed therebetween. An aqueous electrolyte (not shown) is held in the electrode group 1. As shown in FIG. 4, a strip-shaped positive electrode side lead 22 is electrically connected to each of a plurality of points on the end of the positive electrode 5 located on the end face of the electrode group 1. Also, a strip-shaped negative electrode side lead 23 is electrically connected to each of a plurality of points on the end of the negative electrode 3 located on this end face. The plurality of positive electrode side leads 22 are electrically connected to the positive electrode tab 16 in a bundled state. The positive electrode side lead 22 and the positive electrode tab 16 constitute a positive electrode terminal. Also, the negative electrode side lead 23 is connected to the negative electrode tab 17 in a bundled state. The negative electrode side lead 23 and the negative electrode tab 17 constitute a negative electrode terminal. A metallic sealing plate 10 is fixed to the opening of the metallic container 2 by welding or the like. The positive electrode tab 16 and the negative electrode tab 17 are each pulled out to the outside through an extraction hole provided in the sealing plate 10. The inner circumferential surface of each extraction hole in the sealing plate 10 is covered with an insulating material to prevent a short circuit due to contact with the positive electrode tab 16 and the negative electrode tab 17.
[0152] 5, the other end of the negative electrode tab 17 is rectangular and is electrically connected to each of a plurality of locations on the end of the negative electrode 3 located on the upper end face of the electrode group 1. Similarly, although not shown, the other end of the positive electrode tab 16 is rectangular and is electrically connected to each of a plurality of locations on the end of the positive electrode 5 located on the upper end face of the electrode group 1.
[0153] 4, a metal sealing plate 10 is fixed to the opening of the metal container 2 by welding or the like. The positive electrode side lead 22 and the negative electrode side lead 23 are each drawn to the outside through an extraction hole provided in the sealing plate 10. A positive electrode gasket 18 and a negative electrode gasket 19 are disposed on the inner circumferential surface of each extraction hole of the sealing plate 10 to prevent a short circuit due to contact with the positive electrode side lead 22 and the negative electrode side lead 23, respectively. By disposing the positive electrode gasket 18 and the negative electrode gasket 19, the airtightness of the rectangular secondary battery 100 can be maintained.
[0154] A control valve 11 (safety valve) is disposed on the sealing plate 10. When the internal pressure in the battery cell increases due to gas generated by electrolysis of the aqueous solvent, the generated gas can be released to the outside from the control valve 11. As the control valve 11, for example, a reset type that operates when the internal pressure becomes higher than a set value and functions as a sealing plug when the internal pressure decreases can be used. Alternatively, a non-reset type control valve that does not recover its function as a sealing plug once it is activated may be used. In FIG. 4, the control valve 11 is disposed in the center of the sealing plate 10, but the control valve 11 may be located at the end of the sealing plate 10. The control valve 11 may be omitted.
[0155] Further, the sealing plate 10 is provided with a liquid inlet 12. The aqueous electrolyte can be injected through this liquid inlet 12. After the aqueous electrolyte is injected, the liquid inlet 12 can be closed with a sealing plug 13. The liquid inlet 12 and the sealing plug 13 may be omitted.
[0156] Fig. 6 is a partially cutaway perspective view that illustrates a further example of the secondary battery according to the third embodiment. Fig. 7 is an enlarged cross-sectional view of part B of the secondary battery illustrated in Fig. 6. Figs. 6 and 7 show an example of a secondary battery 100 that uses an exterior member made of a laminate film as a container.
[0157] The secondary battery 100 shown in Figures 6 and 7 includes an electrode group 1 shown in Figures 6 and 7, an exterior member 2 shown in Figure 6, and an electrolyte (not shown). The electrode group 1 and the electrolyte are housed in the exterior member 2. The electrolyte is held in the electrode group 1.
[0158] The exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.
[0159] The electrode group 1 is a laminated type electrode group, as shown in Fig. 7. The laminated type electrode group 1 has a structure in which negative electrodes 3 and positive electrodes 5 are alternately laminated with separators 4 interposed therebetween.
[0160] The electrode group 1 includes a plurality of negative electrodes 3. Each of the plurality of negative electrodes 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b supported on both sides of the negative electrode current collector 3a. The electrode group 1 also includes a plurality of positive electrodes 5. Each of the plurality of positive electrodes 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b supported on both sides of the positive electrode current collector 5a.
[0161] The negative electrode current collector 3a of each negative electrode 3 includes a portion 3c on one side of which the negative electrode active material-containing layer 3b is not supported on any surface. This portion 3c serves as a negative electrode current collector tab. As shown in FIG. 7, the portion 3c serving as the negative electrode current collector tab does not overlap with the positive electrode 5. The multiple negative electrode current collector tabs (portions 3c) are electrically connected to a strip-shaped negative electrode terminal 6. The tip of the strip-shaped negative electrode terminal 6 is pulled out to the outside of the exterior member 2.
[0162] Although not shown, the positive electrode current collector 5a of each positive electrode 5 includes a portion on one side where the positive electrode active material-containing layer 5b is not supported on any surface. This portion serves as a positive electrode current collector tab. The positive electrode current collector tab does not overlap with the negative electrode 3, similar to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is located on the opposite side of the electrode group 1 to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is electrically connected to a strip-shaped positive electrode terminal 7. The tip of the strip-shaped positive electrode terminal 7 is located on the opposite side to the negative electrode terminal 6, and is drawn out to the outside of the exterior member 2.
[0163] The secondary battery according to the third embodiment includes the separator described above. This separator is difficult for aqueous solvents to permeate and can be thinned. Therefore, the secondary battery according to the third embodiment can achieve high energy density and long life characteristics.
[0164] (Fourth embodiment) According to a fourth embodiment, there is provided a battery pack. The battery pack according to the fourth embodiment includes a plurality of secondary batteries according to the third embodiment.
[0165] In the battery pack according to the fourth embodiment, the individual cells may be electrically connected in series or in parallel, or may be connected in a combination of series and parallel.
[0166] Next, an example of a battery pack according to a fourth embodiment will be described with reference to the drawings.
[0167] Fig. 8 is a perspective view showing an example of a battery pack according to the fourth embodiment. The battery pack 200 shown in Fig. 8 includes five cells 100a to 100e, four bus bars 21, a positive electrode lead 22, and a negative electrode lead 23. Each of the five cells 100a to 100e is a secondary battery according to the third embodiment.
[0168] For example, the bus bar 21 connects the negative terminal 6 of one cell 100a to the positive terminal 7 of the adjacent cell 100b. In this manner, the five cells 100 are connected in series by the four bus bars 21. That is, the battery pack 200 in FIG. 7 is a five-series battery pack.
[0169] 8, the positive electrode terminal 7 of the leftmost cell 100a among the five cells 100a to 100e is connected to a positive electrode lead 22 for external connection. Also, the negative electrode terminal 6 of the rightmost cell 100e among the five cells 100a to 100e is connected to a negative electrode lead 23 for external connection.
[0170] The battery pack according to the fourth embodiment includes the secondary battery according to the third embodiment, and therefore the battery pack according to the fourth embodiment can achieve high energy density and long life characteristics.
[0171] Fifth embodiment According to a fifth embodiment, there is provided a battery pack. The battery pack includes the battery assembly according to the fourth embodiment. The battery pack may include a single secondary battery according to the third embodiment, instead of the battery assembly according to the fourth embodiment.
[0172] The battery pack according to the fifth embodiment may further include a protection circuit. The protection circuit has a function of controlling charging and discharging of the secondary battery. Alternatively, a circuit included in a device (e.g., electronic device, automobile, etc.) that uses the battery pack as a power source may be used as the protection circuit for the battery pack.
[0173] The battery pack according to the fifth embodiment may further include an external terminal for current flow. The external terminal for current flow is for outputting current from the secondary battery to the outside and / or for inputting current from the outside to the secondary battery. In other words, when the battery pack is used as a power source, current is supplied to the outside through the external terminal for current flow. When the battery pack is charged, a charging current (including regenerative energy from the power of an automobile or the like) is supplied to the battery pack through the external terminal for current flow.
[0174] Next, an example of a battery pack according to a fifth embodiment will be described with reference to the drawings.
[0175] Fig. 9 is an exploded perspective view showing an example of a battery pack according to a fifth embodiment, and Fig. 10 is a block diagram showing an example of an electric circuit of the battery pack shown in Fig. 9.
[0176] The battery pack 300 shown in Figs. 9 and 10 includes a container 31, a lid 32, a protective sheet 33, a battery pack 200, a printed wiring board 34, wiring 35, and an insulating plate (not shown).
[0177] 9 is a bottomed, square container having a rectangular bottom. The container 31 is configured to be able to accommodate a protective sheet 33, a battery pack 200, a printed wiring board 34, and wiring 35. The lid 32 has a rectangular shape. The lid 32 covers the container 31 to accommodate the battery pack 200 and the like. Although not shown, the container 31 and the lid 32 are provided with openings or connection terminals for connection to an external device or the like.
[0178] The battery pack 200 includes a plurality of cells 100, a positive electrode lead 22, a negative electrode lead 23, and an adhesive tape 24.
[0179] At least one of the plurality of cells 100 is a secondary battery according to the third embodiment. The plurality of cells 100 are stacked in a manner that aligns the negative electrode terminal 6 and the positive electrode terminal 7 extending outwardly in the same direction. Each of the plurality of cells 100 is electrically connected in series as shown in FIG. 10. The plurality of cells 100 may be electrically connected in parallel, or may be connected in a combination of series and parallel connections. When the plurality of cells 100 are connected in parallel, the battery capacity is increased compared to when they are connected in series.
[0180] The adhesive tape 24 fastens the plurality of unit cells 100. The plurality of unit cells 100 may be fixed using heat shrink tape instead of the adhesive tape 24. In this case, the protective sheets 33 are disposed on both side surfaces of the battery pack 200, the heat shrink tape is wrapped around the battery pack 200, and the heat shrink tape is then thermally shrunk to bind the plurality of unit cells 100 together.
[0181] One end of the positive electrode lead 22 is connected to the positive electrode terminal 7 of the cell 100 located in the bottom layer in the stack of the cells 100. One end of the positive electrode lead 22 is connected to the negative electrode terminal 6 of the cell 100 located in the top layer in the stack of the cells 100.
[0182] The printed wiring board 34 is disposed along one of the short side surfaces of the inner surface of the container 31. The printed wiring board 34 includes a positive connector 341, a negative connector 342, a thermistor 343, a protection circuit 344, wires 345 and 346, an external terminal 347 for current supply, a positive wire 348a, and a negative wire 348b. One main surface of the printed wiring board 34 faces the surface of the battery pack 200 from which the negative terminal 6 and the positive terminal 7 extend. An insulating plate (not shown) is interposed between the printed wiring board 34 and the battery pack 200.
[0183] The positive electrode side connector 341 has a through hole. The other end of the positive electrode side lead 22 is inserted into this through hole, thereby electrically connecting the positive electrode side connector 341 and the positive electrode side lead 22. The negative electrode side connector 342 has a through hole. The other end of the negative electrode side lead 23 is inserted into this through hole, thereby electrically connecting the negative electrode side connector 342 and the negative electrode side lead 23.
[0184] The thermistor 343 is fixed to one main surface of the printed wiring board 34. The thermistor 343 detects the temperature of each of the cells 100, and transmits a detection signal thereto to the protection circuit 344.
[0185] The external terminal 347 for current supply is fixed to the other main surface of the printed wiring board 34. The external terminal 347 for current supply is electrically connected to a device present outside the battery pack 300.
[0186] The protection circuit 344 is fixed to the other main surface of the printed wiring board 34. The protection circuit 344 is connected to an external terminal 347 for electrical conduction via a positive side wiring 348a. The protection circuit 344 is connected to an external terminal 347 for electrical conduction via a negative side wiring 348b. The protection circuit 344 is also electrically connected to the positive electrode side connector 341 via a wiring 345. The protection circuit 344 is electrically connected to the negative electrode side connector 342 via a wiring 346. Furthermore, the protection circuit 344 is electrically connected to each of the plurality of single cells 100 via the wiring 35.
[0187] The protective sheet 33 is disposed on both inner surfaces in the long side direction of the container 31 and on the inner surface in the short side direction that faces the printed wiring board 34 via the battery pack 200. The protective sheet 33 is made of, for example, resin or rubber.
[0188] The protection circuit 344 controls charging and discharging of the multiple cells 100. The protection circuit 344 also cuts off electrical connection between the protection circuit 344 and an external terminal 347 for current flow, based on a detection signal transmitted from the thermistor 343, or a detection signal transmitted from each of the cells 100 or the battery pack 200.
[0189] An example of the detection signal transmitted from the thermistor 343 is a signal that detects that the temperature of the cell 100 is equal to or higher than a predetermined temperature. An example of the detection signal transmitted from each cell 100 or the battery pack 200 is a signal that detects overcharging, overdischarging, and overcurrent of the cell 100. When detecting overcharging or the like for each cell 100, the battery voltage may be detected, or the positive electrode potential or the negative electrode potential may be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each cell 100.
[0190] The protection circuit 344 may be a circuit included in a device (such as an electronic device or an automobile) that uses the battery pack 300 as a power source.
[0191] As described above, the battery pack 300 includes the external terminal 347 for current supply. Therefore, the battery pack 300 can output a current from the assembled battery 200 to an external device and input a current from the external device to the assembled battery 200 via the external terminal 347 for current supply. In other words, when the battery pack 300 is used as a power source, the current from the assembled battery 200 is supplied to the external device through the external terminal 347 for current supply. When the battery pack 300 is charged, a charging current from the external device is supplied to the battery pack 300 through the external terminal 347 for current supply. When the battery pack 300 is used as an in-vehicle battery, regenerative energy of the vehicle's power can be used as the charging current from the external device.
[0192] The battery pack 300 may include a plurality of assembled batteries 200. In this case, the assembled batteries 200 may be connected in series, in parallel, or in a combination of series and parallel connections. The printed wiring board 34 and the wiring 35 may be omitted. In this case, the negative electrode lead 23 and the positive electrode lead 22 may be used as external terminals for current flow.
[0193] Such a battery pack is used in applications that require excellent cycle performance, for example, when a large current is drawn. Specifically, the battery pack is used as a power source for electronic devices, a stationary battery, and an on-board battery for various vehicles. An example of the electronic device is a digital camera. The battery pack is particularly suitable for use as an on-board battery.
[0194] The battery pack according to the fifth embodiment includes the secondary battery according to the third embodiment or the battery pack according to the fourth embodiment. Therefore, the battery pack according to the fifth embodiment can achieve high energy density and long life characteristics.
[0195] Sixth embodiment According to a sixth embodiment, a vehicle is provided. The vehicle is equipped with the battery pack according to the fifth embodiment.
[0196] In the vehicle according to the sixth embodiment, the battery pack recovers, for example, regenerative energy of the vehicle's motive power. The vehicle according to the sixth embodiment includes a mechanism for converting the kinetic energy of the vehicle into regenerative energy.
[0197] Examples of the vehicle according to the sixth embodiment include a two-wheeled to four-wheeled hybrid electric vehicle, a two-wheeled to four-wheeled electric vehicle, an electric-assisted bicycle, and a railroad car.
[0198] The mounting position of the battery pack in the vehicle according to the sixth embodiment is not particularly limited. For example, when the battery pack is mounted in an automobile, the battery pack can be mounted in the engine compartment, the rear of the vehicle body, or under the seat of the vehicle.
[0199] The vehicle according to the sixth embodiment may be equipped with a plurality of battery packs. In this case, the battery packs may be electrically connected in series, electrically connected in parallel, or electrically connected in a combination of series and parallel connections.
[0200] Next, an example of a vehicle according to a sixth embodiment will be described with reference to the drawings.
[0201] FIG. 11 is a cross-sectional view that illustrates an example of a vehicle according to the sixth embodiment.
[0202] A vehicle 400 shown in Fig. 11 includes a vehicle body 40 and a battery pack 300 according to the fifth embodiment. In the example shown in Fig. 11, the vehicle 400 is a four-wheeled automobile.
[0203] The vehicle 400 may be equipped with a plurality of battery packs 300. In this case, the battery packs 300 may be connected in series, in parallel, or in a combination of series and parallel connections.
[0204] 11 illustrates an example in which the battery pack 300 is mounted in an engine room located in the front of the vehicle body 40. As described above, the battery pack 300 may be mounted, for example, in the rear of the vehicle body 40 or under a seat. This battery pack 300 can be used as a power source for the vehicle 400. In addition, this battery pack 300 can recover regenerative energy for the motive power of the vehicle 400.
[0205] The vehicle according to the sixth embodiment is equipped with the battery pack according to the fifth embodiment. Therefore, the vehicle according to the sixth embodiment can achieve high energy density and long life characteristics.
[0206] Seventh embodiment According to the seventh embodiment, a stationary power source is provided. This stationary power source is equipped with the battery pack according to the fifth embodiment. This stationary power source may be equipped with the assembled battery according to the fourth embodiment or the secondary battery according to the third embodiment instead of the battery pack according to the fifth embodiment.
[0207] The stationary power supply according to the seventh embodiment is equipped with the battery pack according to the fifth embodiment. Therefore, the stationary power supply according to the seventh embodiment can achieve a long life.
[0208] FIG. 12 is a block diagram showing an example of a system including a stationary power source according to the sixth embodiment. FIG. 12 is a diagram showing an example of application to stationary power sources 112 and 123 as an example of use of the battery packs 300A and 300B according to the fifth embodiment. In the example shown in FIG. 12, a system 110 in which the stationary power sources 112 and 123 are used is shown. The system 110 includes a power plant 111, a stationary power source 112, a consumer-side power system 113, and an energy management system (EMS) 115. In addition, a power grid 116 and a communication network 117 are formed in the system 110, and the power plant 111, the stationary power source 112, the consumer-side power system 113, and the EMS 115 are connected via the power grid 116 and the communication network 117. The EMS 115 uses the power grid 116 and the communication network 117 to perform control to stabilize the entire system 110.
[0209] The power plant 111 generates a large amount of power using fuel sources such as thermal power and atomic power. Power is supplied from the power plant 111 through a power grid 116 or the like. A battery pack 300A is mounted on the stationary power source 112. The battery pack 300A can store the power supplied from the power plant 111. The stationary power source 112 can supply the power stored in the battery pack 300A through the power grid 116 or the like. The system 110 is provided with a power conversion device 118. The power conversion device 118 includes a converter, an inverter, a transformer, and the like. Thus, the power conversion device 118 can perform conversion between direct current and alternating current, conversion between alternating currents having different frequencies, and voltage transformation (boosting and bucking), and the like. Thus, the power conversion device 118 can convert the power from the power plant 111 into power that can be stored in the battery pack 300A.
[0210] The consumer-side power system 113 includes a power system for a factory, a power system for a building, a power system for a home, etc. The consumer-side power system 113 includes a consumer-side EMS 121, a power conversion device 122, and a stationary power source 123. The stationary power source 123 is equipped with a battery pack 300B. The consumer-side EMS 121 performs control to stabilize the consumer-side power system 113.
[0211] The consumer-side power system 113 is supplied with power from the power plant 111 and power from the battery pack 300A through the power grid 116. The battery pack 300B can store the power supplied to the consumer-side power system 113. Similarly to the power conversion device 118, the power conversion device 121 includes a converter, an inverter, a transformer, and the like. Therefore, the power conversion device 121 can perform conversion between DC and AC, conversion between ACs with different frequencies, and voltage transformation (boost and step-down), etc. Therefore, the power conversion device 121 can convert the power supplied to the consumer-side power system 113 into power that can be stored in the battery pack 300B.
[0212] The power stored in the battery pack 300B can be used, for example, to charge a vehicle such as an electric car. The system 110 may also be provided with a natural energy source. In this case, the natural energy source generates power using natural energy such as wind power and solar power. Power is supplied from the natural energy source in addition to the power plant 111 through the power grid 116.
[0213] [Example] Examples are described below. The embodiments are not limited to the following examples.
[0214] Example 1 <Preparation of positive electrode> The positive electrode was prepared as follows. First, the positive electrode active material, the conductive agent, and the binder were dispersed in N-methyl-2-pyrrolidone (NMP) solvent to prepare a slurry. The proportions of the positive electrode active material, the conductive agent, and the binder were 91 mass%, 4.5 mass%, and 4.5 mass%, respectively. A lithium manganese composite oxide (LiMn2O4) having a spinel structure and an average particle size of 10 μm was used as the positive electrode active material. The lithium ion absorption and release potential of the lithium manganese composite oxide was 3.5 V (vs. Li / Li + ) or more 4.2V (vs.Li / Li + ) or less. Graphite powder was used as the conductive agent. Polyvinylidene fluoride (PVdF) was used as the binder.
[0215] The prepared slurry was then applied to both sides of a positive electrode current collector, and the coating was dried to form a positive electrode active material-containing layer. A Ti foil having a thickness of 12 μm was used as the positive electrode current collector. The positive electrode current collector and the positive electrode active material-containing layer were then pressed together to produce a positive electrode. The density of the positive electrode active material-containing layer was 3.0 g / cm 3 It was.
[0216] <Preparation of negative electrode> The negative electrode was prepared as follows. First, a negative electrode active material, a conductive agent, and a binder were dispersed in an NMP solvent to prepare a slurry. As the negative electrode active material, lithium titanium oxide (Li4Ti5O 12 The lithium ion absorption and desorption potential of lithium titanium oxide is 1.5V (vs. Li / Li + ) or more than 1.7V (vs. Li / Li + ) or less. Graphite powder was used as the conductive agent. Polyvinyl butyral (PVB) was used as the binder. The proportions of the negative electrode active material, conductive agent, and binder were 94.3 mass%, 4.7 mass%, and 1.0 mass%, respectively.
[0217] Next, the obtained slurry was applied to a negative electrode current collector, and the coating was dried to form a negative electrode active material-containing layer. A 50 μm-thick Zn foil was used as the negative electrode current collector. Here, when applying the slurry to the Zn foil, the slurry was applied only to one side of the Zn foil for the portion located at the outermost periphery of the electrode group of the negative electrode to be produced, and the slurry was applied to both sides of the Zn foil for the other portion. Next, the negative electrode current collector and the negative electrode active material-containing layer were pressed to obtain a negative electrode. The density of the negative electrode active material-containing layer was 2.0 g / cm 3 It was.
[0218] <Preparation of separator> The glass solid electrolyte LATP(Li 1.5 Al 0.5 Ti 1.5(PO4)3), polyvinyl butyral (PVB) as a polymer binder, cellulose nanofiber as a fibrous material, and N-methyl-2-pyrrolidone (NMP) as a solvent were mixed using a planetary mixer to obtain a slurry. The average particle diameter of the LATP particles was 1.0 μm. The average fiber diameter of the cellulose nanofiber was 15 nm. The slurry was adjusted so that the mass ratio of the LATP particles, PVB resin, and cellulose nanofiber was 84% LATP particles, 15% PVB resin, and 1% cellulose nanofiber, that is, LATP particles:PVB resin:cellulose nanofiber was 84:15:1 when the total mass of the LATP particles, PVB resin, and cellulose nanofiber was taken as 100%. The solid content concentration in the slurry was 50% by mass.
[0219] The slurry was then poured into a Teflon (registered trademark) mold and dried in a vacuum oven at 50 degrees Celsius for 24 hours to remove the NMP solvent. The thickness of the resulting separator was 20 μm. In this separator, the proportion of LATP particles was 84% by mass, the proportion of PVB resin was 15% by mass, and the proportion of cellulose nanofibers was 1% by mass. Hereinafter, this separator is referred to as separator SP1. A plurality of separators SP1 were produced.
[0220] <Preparation of electrode groups> A laminate was obtained by laminating the positive electrode, the first separator SP1, the negative electrode, and the second separator SP1 in this order. Next, this laminate was spirally wound so that the negative electrode was disposed at the outermost periphery to produce an electrode group. This was hot-pressed at 130°C to produce a flat electrode group. The obtained electrode group was stored in a thin metal can made of stainless steel with a thickness of 0.25 mm. The metal can used had a valve that leaks gas when the internal pressure reaches 2 atmospheres or more.
[0221] <Preparation of aqueous electrolyte> Lithium chloride (LiCl) was dissolved in water to obtain a liquid aqueous electrolyte, the molar concentration of LiCl in the aqueous electrolyte being 12 mol / L.
[0222] <Preparation of secondary battery and initial charge / discharge> A liquid aqueous electrolyte was poured into the metal can containing the electrode group to prepare three secondary batteries. Each secondary battery was then left for 24 hours in a 25°C environment. After that, the secondary batteries were subjected to an initial charge / discharge in a 25°C environment. In the initial charge / discharge, the secondary batteries were first charged at a constant current equivalent to a 1C rate until the voltage of the secondary batteries reached 2.7V, and then discharged at a constant current equivalent to a 1C rate until the voltage reached 2.1V.
[0223] <Evaluation method> Below, we will explain a method for evaluating the mass ratio of the inorganic particles, polymer binder, and fibrous material contained in the separator, a method for measuring the average fiber diameter of the fibrous material, and a method for measuring the charge capacity and charge / discharge efficiency of the produced secondary battery.
[0224] (Evaluation of the mass ratio of inorganic particles, polymer binder, and fibrous material contained in the separator) One of the secondary batteries was disassembled, and the separator was taken and thoroughly dried under conditions such as 50 degrees Celsius in air. Then, a part of this separator was cut out to obtain a test piece. The size of the test piece was a square plate with a side length of 2 cm. The test piece was thoroughly dried in advance under conditions such as 50 degrees Celsius in air. Next, the test piece was mixed with a sufficient amount of solvent. After dissolving the polymer binder, a centrifuge was used to separate the solid matter and the solvent in which the fibrous material had dissolved. The solid matter was thoroughly dried and then subjected to thermogravimetric analysis (TG) to obtain the mass of the inorganic particles and polymer binder contained in the solid matter. Meanwhile, thermogravimetric analysis (TG) was performed on the solution to obtain the mass of the solvent and fibrous material contained in the solution. From the above, the mass ratio of the inorganic particles, the fibrous material, and the polymer binder was obtained. The mass ratios of the inorganic particles, the polymer binder, and the fibrous material were 84%, 15%, and 1%, respectively.
[0225] (Method for measuring average fiber diameter of fibrous material) One of the secondary batteries was disassembled, and the separator was taken out and thoroughly dried. The separator surface was gold sputtered and then observed using a scanning electron microscope (SEM). The fiber diameter of the fibrous material seen in the SEM photograph was measured at 10 points, and the average of these measurements was calculated as the average fiber diameter.
[0226] (Charge / discharge efficiency and 10-second resistance measurement) A charge / discharge test was carried out using one of the secondary batteries produced, and the charge / discharge efficiency and 10-second resistance value were measured. First, each secondary battery was charged at a constant current of 5A in an environment of 25°C until the battery voltage reached 2.8V. Then, this state was maintained for 30 minutes. Then, the battery was discharged at a constant current of 5A until the battery voltage reached 2.1V. Then, this state was maintained for 30 minutes. This series of operations constituted one charge / discharge cycle, and this was repeated 50 times. Then, in the 51st cycle, the battery was charged at a constant current of 5A, and after maintaining the charge for 30 minutes, it was discharged until the battery voltage reached 2.5V. The ratio of the discharge capacity and the charge capacity at the 50th cycle (discharge capacity / charge capacity) was calculated to obtain the charge / discharge efficiency. Then, immediately after the discharge of the 51st cycle, the 10-second resistance was measured. In the secondary battery after the discharge of the 51st cycle, discharge was performed at a constant current of 5A for 10 seconds. The change in voltage during this time was divided by the applied current of 5 A to obtain the resistance value at a battery voltage of 2.5 V, i.e., the 10-second resistance value. The obtained charge / discharge efficiency and 10-second resistance value of the secondary battery are shown in Table 3.
[0227] Example 2 In preparing the separator, inorganic particles LATP, polymer binder PVB, and cellulose nanofibers as fibrous materials were mixed in a mass ratio of 84:15:1 as raw materials, and NMP was added to prepare a slurry. The obtained slurry was applied to one side of a cellulose nonwoven fabric as a porous free-standing film having a thickness of 15 μm by a doctor blade method, and dried in the air at 120 degrees Celsius to prepare a separator. A secondary battery was also prepared using the obtained separator in the same manner as in Example 1. In this case, in the obtained separator, the cellulose nonwoven fabric was laminated so as to face the negative electrode via the inorganic particle layer. Hereinafter, this separator is referred to as separator SP2. Evaluation was performed in the same manner as described in Example 1, except that separator SP2 was used instead of separator SP1.
[0228] Example 3 The separator was produced in the same manner as described in Example 1, except that polyvinyl alcohol fiber (PVA) was used as the fibrous material. A secondary battery was then produced in the same manner as in Example 1 using the resulting separator.
[0229] Hereinafter, this separator is referred to as separator SP3. Evaluation was performed in the same manner as in Example 1, except that separator SP3 was used instead of separator SP1. Separator SP3 was prepared by mixing inorganic particles LATP, polymer binder PVB, and polyvinyl alcohol fiber (PVA) as a fibrous material in a mass ratio of 84:15:1, adding N-methyl-2-pyrrolidone (NMP), and mixing using a planetary mixer to obtain a slurry with a solid content concentration of 50 mass%. At this time, the average particle diameter of the LATP particles was 1.0 μm, and the polyvinyl alcohol fiber (PVA) had a molecular weight of 1 million or more and an average fiber diameter of 15 nm.
[0230] Example 4 A separator was produced in the same manner as described in Example 1, except that a mixture of polyvinyl alcohol fiber (PVA) and polyacrylic acid was used as the fibrous material, and then a secondary battery was produced using the resulting separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP4. Evaluation was performed in the same manner as in Example 1, except that separator SP4 was used instead of separator SP1.
[0231] Separator SP4 was prepared by mixing inorganic particles LATP, polymer binder PVB, and a mixture of polyvinyl alcohol fiber (PVA) and polyacrylic acid as fibrous material in a mass ratio of 84:15:0.5:0.5 to obtain a slurry. The polyvinyl alcohol fiber (PVA) and polyacrylic acid used had molecular weights of 1 million or more and average fiber diameters of 15 nm.
[0232] Example 5 In preparing the separator, the raw material inorganic particles LATP, the polymer binder PVB, and the fibrous material cellulose nanofiber were mixed in a mass ratio of 84.2:15:0.8 to prepare a slurry, and then the separator was prepared in the same manner as described in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP5. A secondary battery was obtained and evaluated in the same manner as in Example 1, except that separator SP5 was used instead of separator SP1.
[0233] Example 6 In preparing the separator, the raw material inorganic particles LATP, polymer binder PVB, and cellulose nanofiber were mixed in a mass ratio of 84.8:15:0.2 to prepare a slurry, and then the separator was prepared in the same manner as described in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP6. Evaluation was performed in the same manner as in Example 1, except that separator SP6 was used instead of separator SP1.
[0234] Example 7 In preparing the separator, the raw material inorganic particles LATP, polymer binder PVB, and fibrous material cellulose nanofiber were mixed in a mass ratio of 70:15:15 to prepare a slurry, and then the separator was prepared in the same manner as described in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP7. Evaluation was performed in the same manner as in Example 1, except that separator SP7 was used instead of separator SP1.
[0235] Example 8 In preparing the separator, the raw material inorganic particles LATP, polymer binder PVB, and fibrous material cellulose nanofiber were mixed in a mass ratio of 55:15:30 to prepare a slurry, and then the separator was prepared in the same manner as described in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP8. Evaluation was performed in the same manner as in Example 1, except that separator SP8 was used instead of separator SP1.
[0236] Example 9 In preparing the separator, the raw material inorganic particles LATP, the polymer binder PVB, and the fibrous material polyvinyl alcohol fiber (PVA) were mixed in a mass ratio of 84.2:15:0.8 to prepare a slurry, and then the separator was prepared in the same manner as described in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. At this time, the polyvinyl alcohol fiber (PVA) had a molecular weight of 1 million or more and an average fiber diameter of 15 nm. Hereinafter, this separator is referred to as separator SP9. Evaluation was performed in the same manner as in Example 1, except that separator SP9 was used instead of separator SP1.
[0237] Example 10 In preparing the separator, the inorganic particles LATP as the raw material, the polymer binder PVB, and the fibrous material polyvinyl alcohol fiber (PVA) were mixed in a mass ratio of 70:15:15 to prepare a slurry, and then the separator was prepared in the same manner as described in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. At this time, the polyvinyl alcohol fiber (PVA) had a molecular weight of 1 million or more and an average fiber diameter of 15 nm. Hereinafter, this separator is referred to as separator SP10. Evaluation was performed in the same manner as in Example 1, except that separator SP10 was used instead of separator SP1.
[0238] Example 11 In preparing the separator, a separator was prepared in the same manner as described in Example 1, except that a cellulose nanofiber having an average fiber diameter of 5 nm was used as a fibrous material, and then a secondary battery was prepared in the same manner as in Example 1 using the obtained separator. Hereinafter, this separator is referred to as separator SP11. Evaluation was performed in the same manner as in Example 1, except that separator SP11 was used instead of separator SP1.
[0239] Example 12 In preparing the separator, a fibrous material, polyvinyl alcohol fiber (PVA), was used, and a separator having an average fiber diameter of 5 nm was used in the same manner as described in Example 3. A secondary battery was then prepared using the obtained separator in the same manner as in Example 1. At this time, the polyvinyl alcohol fiber (PVA) had a molecular weight of 1 million or more. Hereinafter, this separator is referred to as separator SP12. Evaluation was performed in the same manner as in Example 1, except that separator SP12 was used instead of separator SP1.
[0240] Example 13 In preparing the separator, a mixture of glass solid electrolyte LATP and alumina (Al2O3) was used as inorganic particles, and then a separator was prepared in the same manner as in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP13. Evaluation was performed in the same manner as in Example 1, except that separator SP13 was used instead of separator SP1.
[0241] In preparing the separator SP13, the mass ratio of LATP and alumina in the inorganic particles was set to 50:50, and the LATP particles, alumina particles, polymer binder PVB, and fibrous material cellulose nanofiber were mixed to a mass ratio of 42:42:15:1 to prepare a slurry, and the separator SP13 was prepared by the same method as that described in Example 1. The mass ratio of LATP and alumina in the inorganic particles was evaluated as follows using an X-ray diffractometer (X-ray Powder Diffraction; XRD). First, one of the secondary batteries prepared was disassembled, and the separator SP13 was collected and then dried thoroughly under the condition of 50 degrees Celsius in the atmosphere. Next, a part of the separator SP13 was cut out to obtain a test piece. The size of the test piece was a square plate of 1 cm square. The obtained test piece was set in a sample holder and measured. The mass ratio of LATP and alumina in the inorganic particles was estimated by performing a multiphase analysis of the obtained XRD by the Rietveld method. As a result, the mass ratio of LATP to alumina in the separator SP13 was 50:50. From the above, the mass ratio of the LATP particles, alumina, polymer binder, and fibrous material was 42:42:15:1.
[0242] Example 14 In preparing the separator, a separator was prepared in the same manner as in Example 1 except that a mixture of glass solid electrolyte LATP and alumina was used as inorganic particles, and then a secondary battery was prepared in the same manner as in Example 1 using the obtained separator. Hereinafter, this separator is referred to as separator SP14. Evaluation was performed in the same manner as in Example 1 except that separator SP14 was used instead of separator SP1. In preparing separator SP14, the mass ratio of LATP and alumina in the inorganic particles was set to 50:50, and LATP particles, alumina, polymer binder PVB, and cellulose nanofibers, which are fibrous substances, were mixed in a mass ratio of 42.1:42.1:15:0.8 to prepare a slurry. The separator SP14 was prepared in the same manner as in Example 1. The resulting separator SP14 was evaluated in the same manner as in Example 13, and the mass fractions of the LATP particles, alumina, polymer binder, and fibrous material were found to be 42.1:42.1:15:0.8, respectively.
[0243] Example 15 In preparing the separator, a separator was prepared in the same manner as in Example 1, except that a mixture of glass solid electrolyte LATP( and alumina was used as the inorganic particles, and then a secondary battery was prepared in the same manner as in Example 1 using the obtained separator. Hereinafter, this separator is referred to as separator SP15. Evaluation was performed in the same manner as in Example 1, except that separator SP15 was used instead of separator SP1. In preparing separator SP15, the mass ratio of LATP and alumina in the inorganic particles was 50:50, and LATP particles, alumina particles, polymer binder PVB, and cellulose nanofibers, which are fibrous substances, were mixed in a mass ratio of 35:35:15:15 to prepare a slurry. Separator SP15 was prepared in the same manner as in Example 13. The obtained separator SP15 was evaluated in the same manner as in Example 13, and the mass fractions of LATP particles, alumina, PVB resin, and cellulose nanofibers, respectively, were 35:35:15:15.
[0244] Example 16 In preparing the separator, the inorganic particles LATP, the polymer binder PVB, and the cellulose nanofiber, which is a fibrous material, were mixed in a mass ratio of 84.9:15:0.1 to prepare a slurry, and then the separator was prepared in the same manner as in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP16. Evaluation was performed in the same manner as in Example 1, except that separator SP16 was used instead of separator SP1.
[0245] (Example 17) In preparing the separator, the raw material inorganic particles LATP, polymer binder PVB, and fibrous material cellulose nanofiber were mixed in a mass ratio of 47:15:38 to prepare a slurry, and then the separator was prepared in the same manner as in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP17. Evaluation was performed in the same manner as in Example 1, except that separator SP17 was used instead of separator SP1.
[0246] (Example 18) In preparing the separator, a separator was prepared in the same manner as in Example 1, except that alumina was used as the inorganic particles, and then a secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP18. Evaluation was performed in the same manner as in Example 1, except that separator SP18 was used instead of separator SP1.
[0247] (Example 19) In preparing the separator, a separator was prepared in the same manner as in Example 1, except that silica (SiO2) was used as the inorganic particles, and then a secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP19. Evaluation was performed in the same manner as in Example 1, except that separator SP19 was used instead of separator SP1.
[0248] (Example 20) In preparing the separator, a separator was prepared in the same manner as in Example 1, except that polyvinylidene fluoride (PVdF) was used as a polymer binder, and then a secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP20. Evaluation was performed in the same manner as in Example 1, except that separator SP20 was used instead of separator SP1.
[0249] Example 21 In preparing the separator, the raw material inorganic particles LATP, polymer binder PVB, and fibrous material cellulose nanofiber were mixed in a mass ratio of 89:10:1 to prepare a slurry, and then the separator was prepared in the same manner as in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP21. Evaluation was performed in the same manner as in Example 1, except that separator SP21 was used instead of separator SP1.
[0250] Example 22 In preparing the separator, the raw material inorganic particles LATP, polymer binder PVB, and fibrous material polyvinyl alcohol fiber (PVA) were mixed in a mass ratio of 89:10:1 to prepare a slurry, and then a separator was prepared in the same manner as in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. At this time, polyvinyl alcohol fiber (PVA) with a molecular weight of 1 million or more and an average fiber diameter of 15 nm was used. Hereinafter, this separator is referred to as separator SP22. A secondary battery was obtained and evaluated in the same manner as in Example 1, except that separator SP22 was used instead of separator SP1.
[0251] (Example 23) In preparing the separator, the raw material inorganic particles LATP, polymer binder PVB, and fibrous material cellulose nanofiber were mixed in a mass ratio of 65:15:20 to prepare a slurry, and then a separator was prepared in the same manner as in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP23. A secondary battery was obtained and evaluated in the same manner as in Example 1, except that separator SP23 was used instead of separator SP1.
[0252] Example 24 In preparing the separator, the raw material inorganic particles LATP, polymer binder PVB, and fibrous material cellulose nanofiber were mixed in a mass ratio of 84.2:15:0.8 to prepare a slurry, and then the separator was prepared in the same manner as in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. Hereinafter, this separator is referred to as separator SP24. Evaluation was performed in the same manner as in Example 1, except that separator SP24 was used instead of separator SP1.
[0253] (Example 25) In preparing the separator, the inorganic particles LATP as the raw material, the polymer binder PVB, and the fibrous material polyvinyl alcohol fiber (PVA) were mixed in a mass ratio of 84.8:15:0.2 to prepare a slurry, and then the separator was prepared in the same manner as in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. At this time, the polyvinyl alcohol fiber (PVA) had a molecular weight of 1 million or more and an average fiber diameter of 15 nm. Hereinafter, this separator is referred to as separator SP25. A secondary battery was obtained and evaluated in the same manner as in Example 1, except that separator SP25 was used instead of separator SP1.
[0254] (Example 26) In preparing the separator, the inorganic particles LATP as the raw material, the polymer binder PVB, and the fibrous material polyvinyl alcohol fiber (PVA) were mixed in a mass ratio of 70:15:15 to prepare a slurry, and then the separator was prepared in the same manner as in Example 1. A secondary battery was prepared using the obtained separator in the same manner as in Example 1. At this time, the polyvinyl alcohol fiber (PVA) had a molecular weight of 1 million or more and an average fiber diameter of 15 nm. Hereinafter, this separator is referred to as separator SP26. Evaluation was performed in the same manner as in Example 1, except that separator SP26 was used instead of separator SP1.
[0255] Example 27 In preparing the separator, a separator was prepared in the same manner as in Example 1, except that a slurry was prepared by mixing the inorganic particles LATP, the polymer binder PVB, and the fibrous material polyvinyl alcohol fiber (PVA) in a mass ratio of 55:15:30. A secondary battery was then prepared using the obtained separator in the same manner as in Example 1. At this time, the polyvinyl alcohol fiber (PVA) had a molecular weight of 1 million or more and an average fiber diameter of 15 nm. Hereinafter, this separator is referred to as separator SP8. Evaluation was performed in the same manner as in Example 1, except that separator SP27 was used instead of separator SP1.
[0256] (Example 28) In preparing the separator, a separator was prepared in the same manner as in Example 1, except that polyacrylic acid was used as the fibrous material, and then a secondary battery was prepared in the same manner as in Example 1 using the obtained separator. At this time, polyacrylic acid having a molecular weight of 1 million or more and an average fiber diameter of 15 nm was used. Hereinafter, this separator is referred to as separator SP28. Evaluation was performed in the same manner as in Example 1, except that separator SP28 was used instead of separator SP1.
[0257] (Example 29) A separator was produced in the same manner as in Example 1, except that cellulose fibers with an average fiber diameter of 200 nm were used as the fibrous material. Hereinafter, this separator is referred to as separator SP29. A secondary battery was obtained and evaluated in the same manner as in Example 1, except that separator SP29 was used instead of separator SP1.
[0258] Comparative Example 1 A secondary battery was obtained and evaluated in the same manner as described in Example 1, except that a cellulose nonwoven fabric was used instead of the separator SP1. The thickness of this cellulose nonwoven fabric was 20 μm. Hereinafter, this separator is referred to as separator SP30.
[0259] Comparative Example 2 Instead of the separator SP1, a separator SP31 was used, which was prepared in the same manner as the separator SP1, except that it did not contain any fibrous material. In the separator SP31, the slurry was adjusted so that the mass ratio of the LATP particles to the PVB resin was 85:15. A secondary battery was obtained and evaluated in the same manner as in Example 1, except that the separator SP31 was used instead of the separator SP1.
[0260] Comparative Example 3 Instead of the separator SP1, a separator SP32 prepared by the following method was used. Polyvinyl alcohol fiber (PVA) was prepared in the same manner as the separator SP1, except that the slurry was adjusted so that the mass ratio of LATP particles, PVB resin, and polyvinyl alcohol fiber (PVA) having an average fiber diameter of 15 nm was 25:15:60. A secondary battery was obtained and evaluated in the same manner as in Example 1, except that the separator SP32 was used instead of the separator SP1.
[0261] Comparative Example 4 In the manufacture of the separator, the glass solid electrolyte LATP (Li 1.5 Al 0.5 Ti 1.5A separator was produced in the same manner as in Comparative Example 3, except that alumina particles were used instead of (PO4)3) particles, and cellulose nanofibers with an average fiber diameter of 15 nm were used as the fibrous material. Hereinafter, this separator is referred to as separator SP33. A secondary battery was obtained and evaluated in the same manner as in Example 1, except that separator SP33 was used instead of separator SP1. [Table 1] [Table 2] [Table 3] [Table 4]
[0262] In the above Tables 1 and 2, among the columns under the heading "Separator", the columns labeled "Abbreviation", "Inorganic Particles", "Polymer Binder", and "Fibrous Material" each list the abbreviation of the separator, for example SP1, and the type of material used as the inorganic particles, polymer binder, and fibrous material. In addition, in the columns to the right of each of the columns "Inorganic Particles", "Polymer Binder", and "Fibrous Material", the column labeled "Mass Ratio [%]" lists the mass ratio of each material in the separator as a percentage. In the tables, "-" indicates that it is not included.
[0263] In the columns under the heading "Secondary battery performance" in Tables 3 and 4, the column labeled "10-second resistance value [Ω]" lists the resistance value obtained during 10-second discharge after 51 charge-discharge cycles. The column labeled "Charge-discharge efficiency [%]" lists the value obtained by dividing the discharge capacity after 50 charge-discharge cycles by the charge capacity.
[0264] As shown in Table 3, the secondary batteries according to Examples 1 to 29 achieved high charge / discharge efficiency and low 10-second resistance, and thus achieved both long life and low resistance. On the other hand, as shown in Table 4, the secondary batteries according to Comparative Examples 1 to 4 could not achieve both long life and low resistance. This is believed to be because the separator in Comparative Example 1 did not contain inorganic particles or polymer binder, so that water permeation between the positive electrode and the negative electrode could not be suppressed, and water decomposition occurred on the negative electrode side. In addition, the secondary battery according to Comparative Example 2, which did not contain a fibrous material, had a clearly higher 10-second resistance and a lower charge / discharge efficiency than that of Example 1. In Comparative Examples 3 and 4, the weight ratio of the fibrous material was greater than 40 mass%, so that the amount of inorganic particles in the separator was reduced, and further, the mechanical strength of the separator was reduced, and the charge / discharge efficiency was reduced. From the above, it was confirmed that the secondary battery has low resistance when the separator is provided with a fibrous material. This is believed to be because the addition of 0.1% by mass or more and 40% by mass or less of fibrous material to the separator resulted in the aqueous electrolyte being trapped between the fibrous material particles in the separator. The separators including Examples 1 and 8, in which the mass ratio of the fibrous material in the separator was in the range of 0.5% by mass or more and 30% by mass or less, had lower 10-second resistance or higher charge / discharge efficiency than Examples 16 and 17. From this, it is believed that the mass ratio of the fibrous material in the separator is preferably in the range of 0.1% by mass or more and 40% by mass or less, and more preferably in the range of 0.5% by mass or more and 30% by mass or less.
[0265] Even in Examples 13, 18, and 19, in which the type of inorganic particles in the separator was different from that in Example 1, and in Example 20, in which the polymer binder was different, the charge / discharge efficiency and the 10-second resistance value were at the same level as in Example 1. Also, in Examples 21 and 22, in which the ratio of inorganic particles to binder in the separator was different, charge / discharge efficiency and low 10-second resistance were confirmed to be almost the same as in Example 1.
[0266] When the average fiber diameter of the fibrous material in the separator was 5 nm, the charge / discharge efficiency and the 10-second resistance value were both at the same level as the separator in Example 1. On the other hand, when the average fiber diameter of the fibrous material in the separator was 200 nm, the 10-second resistance value was higher than that in Example 1. This indicates that when the average fiber diameter of the fibrous material is 100 nm or less, the separator swells to reduce resistance, and the aqueous electrolyte is effectively incorporated between the fibrous material.
[0267] When the separator having such a configuration according to at least one embodiment described above is used in a secondary battery, the electrolyte penetrates between the fibrous materials, improving ionic conductivity, thereby lowering the resistance of the secondary battery. Therefore, the secondary battery according to at least one embodiment including such a separator can achieve excellent charge / discharge efficiency, i.e., a long life.
[0268] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims. [Explanation of symbols]
[0269] Reference Signs List 1...electrode group, 2...exterior member (container), 3...negative electrode, 3a...negative electrode current collector, 3b...negative electrode active material-containing layer, 4...separator, 5...positive electrode, 5a...positive electrode current collector, 5b...positive electrode active material-containing layer, 6...negative electrode terminal, 7...positive electrode terminal, 10...sealing plate, 11...control valve, 12...filling port, 13...sealing plug, 16...positive electrode tab, 17...negative electrode tab, 18...positive electrode gasket, 19...negative electrode gasket, 21... Bus bar, 22... positive electrode lead (positive electrode side lead), 23... negative electrode lead (negative electrode side lead), 24... adhesive tape, 31... storage container, 32... lid, 33... protective sheet, 34... printed wiring board, 35... wiring, 40... vehicle body, 51... negative electrode, 52... positive electrode, 53... separator, 100... secondary battery, 110... system, 111... power plant, 112... stationary power source, 113... consumer side Power system, 116...power grid, 117...communication network, 118...power conversion device, 121...power conversion device, 122...power conversion device, 123...stationary power source, 200...battery pack, 300...battery pack, 300A...battery pack, 300B...battery pack, 341...positive connector, 342...negative connector, 343...thermistor, 344...protection circuit, 345...wiring, 346...wiring , 347...external terminal for current supply, 348a...positive wiring, 348b...negative wiring, 400...vehicle, 500...secondary battery, 510...negative electrode current collector, 511...negative electrode active material-containing layer, 520...positive electrode current collector, 521...positive electrode active material-containing layer, 530...porous free-standing membrane, 531...inorganic particle layer, 531a...inorganic particles, 533...polymer binder, 54...fibrous material, AE...aqueous electrolyte.
Claims
1. an electrode group including a positive electrode containing a positive electrode active material, a negative electrode containing a negative electrode active material, and a separator located at least between the positive electrode and the negative electrode; An aqueous electrolyte; Equipped with The separator is Inorganic particles; A polymeric binder; A fibrous material; An inorganic particle layer comprising: a ratio of the mass of the fibrous material to the total mass of the inorganic particles, the polymer binder, and the fibrous material is 0.1 mass% or more and 40 mass% or less; a ratio of the mass of the polymer binder to the total mass of the inorganic particles, the polymer binder, and the fibrous material is 5 mass% or more and 30 mass% or less; The average fiber diameter of the fibrous material is 1 nm or more and 30 nm or less. Secondary battery.
2. The fibrous material has hydrophilic functional groups, such as a hydroxyl group, a sulfone group, and a carboxyl group. The secondary battery according to claim 1 .
3. The fibrous material includes one or more materials selected from the group consisting of cellulose fibers, polysaccharides, polyvinyl alcohol, polyacrylic acid, polystyrene sulfonate, polystyrene trialkylbenzylammonium, and derivatives and copolymers thereof; The secondary battery according to claim 1 .
4. a ratio of the mass of the polymer binder to the total mass of the inorganic particles, the polymer binder, and the fibrous material is 10 mass% or more and 30 mass% or less; The secondary battery according to claim 1 .
5. The mass ratio of the fibrous material is 0.5 mass % or more and 30 mass % or less. The secondary battery according to claim 1 .
6. The separator further comprises a porous free-standing membrane disposed on a main surface of the inorganic particle layer. The secondary battery according to claim 1 .
7. The inorganic particles are NASICON type LATP (Li 1+x A x Ti 2-x (P.O. 4 ) 3 ), Li 1+x A x Ge 2-x (P.O. 4 ) 3 , Li 1+x A x Zr 2-x (P.O. 4 ) 3 (0.1≦x≦0.5), amorphous LIPON (Li 2.9 P.O. 3.3 N 0.46 ) or garnet-type LLZ (Li 7 La 3 ZrO 12 ) at least one of The secondary battery according to claim 1 .
8. The polymer binder includes a portion constituted by a monomer unit made of a hydrocarbon having a functional group containing at least one element selected from the group consisting of oxygen (O), sulfur (S), nitrogen (N) and fluorine (F), and the proportion of the portion constituted by the monomer unit is 70 mol % or more. The secondary battery according to claim 1 .
9. The negative electrode active material has a lithium ion absorption / release potential of 1 V or more and 3 V or less (vs. Li / Li) based on metallic lithium. + ) The secondary battery according to claim 1 .
10. The positive electrode active material has a lithium ion absorption / release potential of 2.5 V or more and 5.5 V or less (vs. Li / Li) based on metallic lithium. + ) The secondary battery according to claim 1 .
11. A battery pack comprising the secondary battery according to claim 1 .
12. Further includes an external terminal for current supply and a protection circuit. The battery pack according to claim 11.
13. The battery includes a plurality of the secondary batteries, the plurality of secondary batteries being electrically connected in series, in parallel, or in a combination of series and parallel. The battery pack according to claim 11 or 12.
14. A vehicle comprising the battery pack according to any one of claims 11 to 13.
15. A stationary power source comprising the battery pack according to any one of claims 11 to 13.
Citation Information
Patent Citations
Separator for liquid type lead-acid battery
JP1993054874A
Lead-acid battery separator
JP1994295718A
Solid electrolyte and secondary battery
JP2013232284A
Secondary battery
JP2014207059A
Laminated electrode body having dense electrolyte layer on negative electrode layer side before lamination press
JP2015032535A